Image forming apparatus and image forming method

By using a cleaning scraper with a specific hardness ratio and a surface chemical composition ratio in the image forming device, combined with a specific electrostatic latent image developer and transfer process, the toner film formation and staple marking in the image forming device is solved. The problem has achieved improvement in image quality.

CN119439674APending Publication Date: 2025-02-14FUJIFILM BUSINESS INNOVATION CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410180219.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-02-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when an image forming device uses an intermediate transfer belt, problems of toner film formation and staple marking are likely to occur, which affects image quality.

Method used

The cleaning scraper with a specific hardness ratio and surface chemical composition ratio is used to inhibit the occurrence of toner film formation and staple marking in combination with a specific electrostatic latent image developer and transfer process.

Benefits of technology

The toner film formation on the surface of the intermediate transfer belt is effectively suppressed, and the generation of staple marks on the image is prevented, thereby improving the quality and stability of the image.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439674A_ABST
    Figure CN119439674A_ABST
Patent Text Reader

Abstract

The invention relates to an image forming apparatus and an image forming method. The image forming apparatus includes: an image holder; a charging member; an electrostatic latent image forming member; a developing member accommodating an electrostatic latent image developer containing toner having toner particles, the electrostatic latent image formed on a surface of the image holding body being developed into a toner image by the electrostatic latent image developer; an intermediate transfer belt having an outer peripheral surface for transferring the toner image; a primary transfer member having a primary transfer member that primarily transfers the toner image formed on a surface of an image holding body to an outer peripheral surface of the intermediate transfer belt; a secondary transfer member having a secondary transfer member that secondarily transfers the toner image, which has been primarily transferred onto the outer peripheral surface of the intermediate transfer belt, onto a surface of a recording medium; and a cleaning device having a cleaning blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an image forming device and an image forming method. Background Art

[0002] In an image forming apparatus (copier, fax machine, printer, etc.) using an electrophotographic method, a toner image formed on the surface of an image holding member is transferred to the surface of a recording medium and fixed to the recording medium, thereby forming an image. In addition, when transferring the toner image to the recording medium, for example, an intermediate transfer belt is used, and when cleaning the outer peripheral surface of the intermediate transfer belt, a cleaning blade is used.

[0003] For example, Patent Document 1 discloses "an image forming apparatus comprising: an image carrier; a charging member for charging the surface of the image carrier; a latent image forming member for forming an electrostatic latent image on the charged surface of the image carrier; a developing member for developing the electrostatic latent image formed on the surface of the image carrier into a toner image; a transfer member for transferring the toner image on the surface of the image carrier to a transfer member; and a cleaning member having a cleaning blade, the cleaning blade being in contact with the surface of the image carrier and cleaning the transfer residual toner attached to the surface of the image carrier, the cleaning blade having a short strip-shaped elastic blade and a surface layer, the surface layer covering the front edge of the elastic blade, being harder than the elastic blade, and having a friction coefficient of 0.1 or more and 0.6 or less, the image carrier having a surface protective layer in which fluororesin particles are dispersed, the surface protective layer being formed by applying a coating liquid, the coating liquid being obtained by dispersing fluororesin particles having a volume average particle size of 10 [μm] or less and then irradiating with ultrasonic waves".

[0004] Patent document 2 discloses "a process cartridge comprising: an image carrier; a developing member comprising a toner for developing an electrostatic latent image formed on the image carrier using the toner to form a visible image; and a cleaning member for removing residual toner remaining on the image carrier using a cleaning blade, the cleaning blade comprising an elastic member, the elastic member abutting against a surface of the image carrier and removing the residual toner remaining on the image carrier, the elastic member comprising a substrate and a surface layer provided on the substrate, when a surface of the substrate facing a downstream side of a contact portion of the elastic member (abutting against the image carrier) in a traveling direction of the image carrier is set as a substrate lower surface, the surface layer is formed on at least a portion of the substrate lower surface including the contact portion, the surface layer having a Martens hardness HM measured using a nanoindenter in a film thickness direction that decreases from the surface toward the substrate lower surface, the Martens hardness HM having a measured value under a load of 1 μN and a measured value under a load of 1000 μN being 2.5 N / mm2 Above and 32.5N / mm 2 The average film thickness of the surface layer at the abutting portion is 10 μm to 500 μm, the toner included in the developing member has a circularity of less than 0.950, and a content of fine powder of 2 μm or less is 20% by number to 60% by number.

[0005] Patent document 3 discloses "a cleaning blade formed by cutting a plate-shaped body made of a cured polyurethane resin composition, wherein 4 atom % or more of silicon atoms (Si) are present on the end face of the cleaning blade formed by the cutting due to adhesion and oxidation treatment of an organic siloxane."

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-300751

[0007] Patent Document 2: Japanese Patent Application Publication No. 2021-012342

[0008] Patent Document 3: Japanese Patent Application Publication No. 2001-051565 Summary of the invention

[0009] The object of the present invention is to provide an image forming apparatus and an image forming method which suppress the occurrence of toner filming on the surface of the intermediate transfer belt and suppress the generation of staple marks on the image, compared with a cleaning blade having a ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer of less than 0.84 or greater than 0.93, or a cleaning blade having a total amount of F and Si within 200 nm from the edge layer on the surface in contact with the intermediate transfer belt of less than 75% of the total amount of F and Si within 5 μm from the surface.

[0010] Means for solving the above-mentioned problems include the following.

[0011] <1> An image forming device comprising:

[0012] Image holding body;

[0013] a charging member for charging the surface of the image holding member;

[0014] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;

[0015] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;

[0016] an intermediate transfer belt, the outer peripheral surface of which is used for transferring the toner image;

[0017] a primary transfer member having a primary transfer part for primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt;

[0018] a secondary transfer member having a secondary transfer component for secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to a surface of a recording medium; and

[0019] A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the intermediate transfer belt, and has a double-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer are composed of a polyurethane resin, the ratio of the hardness Hb of the edge layer to the hardness Ha of the back layer (Hb / Ha) is greater than 0.84 and less than 0.93, and the total amount of F and Si existing within 200nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si existing within 5μm from the surface.

[0020] <2> according to <1> The image forming device, wherein:

[0021] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

[0022] <3> according to <1> or <2> The image forming device, wherein:

[0023] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

[0024] <4> according to <1> to <3> The image forming apparatus as described in any one of the preceding claims, wherein:

[0025] The cleaning blade has a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer of 0.87 or more and 0.90 or less.

[0026] <5> according to <1> to <4> The image forming apparatus as described in any one of the preceding claims, wherein:

[0027] The hardness Hb of the edge layer is greater than or equal to 75° and less than 85°, and the hardness Ha of the back layer is greater than or equal to 85° and less than or equal to 95°.

[0028] <6> according to <5> The image forming device, wherein:

[0029] The hardness Hb of the edge layer is greater than or equal to 77° and less than or equal to 83°, and the hardness Ha of the back surface layer is greater than or equal to 87° and less than or equal to 93°.

[0030] <7> according to <1> to <6> The image forming apparatus as described in any one of the preceding claims, wherein:

[0031] In the cleaning blade, a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for 85% or more of a total amount of F and Si present within 5 μm from the surface.

[0032] <8> according to <1> to <7> The image forming apparatus as described in any one of the preceding claims, wherein:

[0033] In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 15 atm % or more.

[0034] <9> according to <8> The image forming device, wherein:

[0035] In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 18 atm % or more and 25 atm % or less.

[0036] <10> according to <1> to <9> The image forming apparatus as described in any one of the preceding claims, wherein:

[0037] In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more.

[0038] <11> according to <10> The image forming device, wherein:

[0039] In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more and 2.0 atm % or less.

[0040] <12> according to <1> to <11> The image forming apparatus as described in any one of the preceding claims, wherein:

[0041] The cleaning blade contains a silicone-based polymer in a surface layer of the edge layer that contacts the intermediate transfer belt.

[0042] <13> according to <1> to <12> The image forming apparatus as described in any one of the preceding claims, wherein:

[0043] The cleaning blade contacts the intermediate transfer belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

[0044] <14> An image forming method, comprising:

[0045] A charging process to charge the surface of the image holding body;

[0046] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;

[0047] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;

[0048] a primary transfer step of primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt;

[0049] a secondary transfer step of secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to the surface of a recording medium; and

[0050] A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the intermediate transfer belt and cleans the same, wherein the cleaning scraper has a double-layer structure consisting of an edge layer and a back layer, wherein the edge layer and the back layer are made of a polyurethane resin, wherein a ratio (Hb / Ha) of a hardness Hb (°) of the edge layer to a hardness Ha (°) of the back layer is greater than or equal to 0.84 and less than or equal to 0.93, and a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of a total amount of F and Si present within 5 μm from the surface.

[0051] Effects of the Invention

[0052] according to <1> The invention involved provides an image forming apparatus that suppresses the occurrence of toner filming on the surface of an intermediate transfer belt and suppresses the occurrence of staple marks on an image, compared to an image forming apparatus having a cleaning blade in which the ratio of the hardness Hb of the edge layer to the hardness Ha of the back layer (Hb / Ha) is less than 0.84 or greater than 0.93, or a cleaning blade in which the total amount of F and Si present within 200 nm from the surface of the edge layer in contact with the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5 μm from the surface.

[0053] according to <2> The present invention provides an image forming apparatus having excellent low-temperature fixing property of an image compared to an image forming apparatus in which the releasing agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the releasing agent in the entire toner particle.

[0054] according to <3> The invention relates to an image forming apparatus that has excellent low-temperature fixability of an image compared to an image forming apparatus having a melting temperature of a release agent exceeding 75° C., and an image forming apparatus that suppresses toner filming on the surface of an intermediate transfer belt compared to an image forming apparatus having a melting temperature of a release agent below 70° C.

[0055] according to <4> The invention provides an image forming apparatus that suppresses toner filming on the surface of an intermediate transfer belt compared to an image forming apparatus having a cleaning blade having a ratio (Hb / Ha) of the hardness Hb of an edge layer to the hardness Ha of a back layer of less than 0.87 or greater than 0.90.

[0056] according to <5> or <6> The invention involves providing an image forming device that suppresses the generation of staple marks on an image compared to an image forming device having an edge layer with a hardness of 85° or more or a cleaning blade with a back layer with a hardness of more than 95°, and provides an image forming device that achieves excellent cleaning performance and suppresses the wear of the cleaning blade compared to an image forming device having an edge layer with a hardness of less than 75°, and provides an image forming device that suppresses the occurrence of lifting on the cleaning blade compared to an image forming device having a back layer with a hardness of less than 85°.

[0057] according to <7> The invention involved provides an image forming apparatus that suppresses the formation of colorant film on the surface of an intermediate transfer belt compared to an image forming apparatus having a cleaning blade in which the total amount of F and Si present within 200 nm from the edge layer of the surface in contact with the intermediate transfer belt is less than 85% of the total amount of F and Si present within 5 μm from the surface.

[0058] according to <8> or <9> The invention provides an image forming apparatus that suppresses toner filming on the surface of an intermediate transfer belt compared to an image forming apparatus having a cleaning blade having a total amount of F and Si on the surface of the edge layer in contact with the intermediate transfer belt of less than 15 atm%.

[0059] according to <10> or <11> The invention involved provides an image forming apparatus that can suppress the occurrence of toner filming on the surface of the intermediate transfer belt in terms of time, compared to an image forming apparatus having a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface of the edge layer in contact with the intermediate transfer belt is less than 0.3 atm%.

[0060] according to <12> The invention provides an image forming apparatus that suppresses toner filming on the surface of an intermediate transfer belt compared to an image forming apparatus having an edge layer and a cleaning blade whose surface layer in contact with the intermediate transfer belt contains a fluorine compound but does not contain a silicone polymer.

[0061] according to <13> The invention involves providing an image forming device that further suppresses the generation of staple marks on an image compared to an image forming device in which a cleaning blade contacts an intermediate transfer belt with a pressing force of less than 1.5 gf / mm, and an image forming device that further suppresses the generation of colorant filming on the surface of the intermediate transfer belt compared to an image forming device in which a cleaning blade contacts an intermediate transfer belt with a pressing force of more than 3.5 gf / mm.

[0062] according to <14> The invention involved provides an image forming method for suppressing toner filming on the surface of an intermediate transfer belt and suppressing the generation of staple marks on an image, compared to an image forming method including a cleaning process using a cleaning blade having a ratio (Hb / Ha) of the hardness Hb of an edge layer to the hardness Ha of a back layer of less than 0.84 or more than 0.93, or a cleaning blade having a total amount of F and Si present within 200 nm from the surface of the edge layer in contact with the intermediate transfer belt of less than 75% of the total amount of F and Si present within 5 μm from the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Embodiments of the present invention will be described in detail with reference to the following drawings.

[0064] Figure 1 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;

[0065] Figure 2 It is a schematic diagram for explaining the amount d of bite of the cleaning blade with respect to the intermediate transfer belt. DETAILED DESCRIPTION

[0066] Hereinafter, the present embodiment as an example of the present invention will be described. These descriptions and examples are for illustrating the embodiment and do not limit the scope of the embodiment.

[0067] In the numerical ranges recorded in stages in this embodiment, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this embodiment, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0068] In the present embodiment, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0069] While the embodiment is described with reference to the drawings in this embodiment, the structure of the embodiment is not limited to the structure shown in the drawings. In addition, the sizes of the components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.

[0070] In this embodiment, each component may include a plurality of corresponding substances. In this embodiment, when the amount of each component in the composition is mentioned, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition.

[0071] [Image forming apparatus]

[0072] The image forming device involved in the present embodiment comprises: an image holder; a charging member for charging the surface of the image holder; an electrostatic latent image forming member for forming an electrostatic latent image on the surface of the charged image holder; a developing member for accommodating an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; an intermediate transfer belt, the outer peripheral surface of which is used to transfer the colorant image; a primary transfer member having a primary transfer member, the primary transfer member primarily transfers the colorant image formed on the surface of the image holder to the outer peripheral surface of the intermediate transfer belt; a secondary transfer member having a secondary transfer member, the secondary transfer member secondarily transfers the colorant image primarily transferred to the outer peripheral surface of the intermediate transfer belt to the surface of a recording medium; and a cleaning device having a cleaning scraper, the cleaning scraper contacts the outer peripheral surface of the intermediate transfer belt and cleans it.

[0073] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.

[0074] The cleaning blade has a double-layer structure consisting of an edge layer and a back layer, and the edge layer and the back layer are made of polyurethane resin. In addition, the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer is 0.84 or more and 0.93 or less. Furthermore, the total amount of F and Si present within 200nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si present within 5μm from the surface.

[0075] With the above-described configuration, the image forming apparatus according to the present embodiment suppresses toner filming on the surface of the intermediate transfer belt and suppresses the generation of staple marks on the image. The reason for this is presumably as follows.

[0076] From the viewpoint of improving the low-temperature fixability of an image, a method of using a toner having toner particles with a low melting temperature wax localized in the surface layer (specifically, a toner in which the release agent present in the region within 800 nm from the surface of the toner particle accounts for more than 70% of the entire release agent of the toner particle, and the melting temperature of the release agent is from 65° C. to 80° C.) has been studied. However, when using toner particles in which a low melting temperature wax is localized in the surface layer, toner filming is sometimes likely to occur on the surface of the intermediate transfer belt when an image with a low image density is repeatedly formed under a high temperature and high humidity environment. It is believed that this is because the toner particles in which the low melting temperature wax is localized in the surface layer as described above will become soft under a high temperature and high humidity environment, resulting in easy crushing. Furthermore, it is believed that this is because by repeatedly forming an image with a low image density, the toner particles present on the intermediate transfer belt will decrease, thereby increasing the pressure applied by the cleaning blade to one toner particle.

[0077] In contrast, a method of suppressing toner filming by adjusting the cleaning blade pressed against the intermediate transfer belt is conceivable. For example, a method of suppressing toner filming by increasing the hardness of the cleaning blade to improve the scraping property can be cited. However, when the hardness of the cleaning blade is increased to improve the scraping property, the followability of the cleaning blade to the opposing surface is reduced, and as a result, a staple mark is sometimes generated in the formed image. In addition, a staple mark refers to an image defect in which two dense dots appear side by side on the image in a direction (width direction) orthogonal to the processing direction (i.e., the traveling direction of the intermediate transfer belt and the conveying direction of the recording medium).

[0078] In contrast, in the image forming apparatus according to the present embodiment, a cleaning blade is used in which the total amount of F and Si present within 200 nm from the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface. That is, in the cleaning blade, F and Si are concentrated near the contact portion with the intermediate transfer belt. By having at least one of F and Si at the contact portion, the friction of the cleaning blade is reduced and the state of the front end of the contact portion becomes stable. Thus, even when using toner particles that cause the wax with a low melting temperature as described above to be concentrated in the surface layer, when repeatedly forming an image with a low image density under a high temperature and high humidity environment, toner filming on the surface of the intermediate transfer belt can be suppressed.

[0079] Furthermore, in the image forming apparatus according to the present embodiment, a cleaning blade having a double-layer structure consisting of an edge layer and a back layer, wherein the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer is 0.84 or more and 0.93 or less is used. That is, a cleaning blade having a double-layer structure and a back layer having a higher hardness than the edge layer is used, thereby improving the followability of the cleaning blade to follow the opposing surface. As a result, the generation of staple marks on the formed image can be suppressed.

[0080] In summary, it is presumed that according to the image forming apparatus according to the present embodiment, it is possible to suppress toner filming on the surface of the intermediate transfer belt and to suppress the generation of staple marks on the image.

[0081] (Toner)

[0082] The toner contained in the electrostatic latent image developer used in the image forming apparatus according to the present embodiment is described. The toner contains toner particles, in which the release agent present in the region within 800 nm from the surface of the toner particles accounts for more than 70% of the release agent in the entire toner particles, and the melting temperature of the release agent is more than 65° C. and less than 80° C.

[0083] The toner particles contain a release agent and may further contain a binder resin. Furthermore, the toner particles may further contain other internal additives such as a colorant.

[0084] -Release agent-

[0085] The melting temperature of the release agent is 65° C. to 80° C., for example, preferably 68° C. to 77° C., more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixability of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, toner filming on the transfer belt surface can be suppressed.

[0086] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for determining the melting temperature in JIS K-7121-1987 “Methods for determining transition temperatures of plastics”.

[0087] Regarding the release agent, 70% or more of all the release agent exists within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent existing within 800 nm from the surface of the toner particles is also referred to as "surface layer proportion of the release agent").

[0088] The surface ratio of the release agent is 70% or more, for example, preferably 75% or more, more preferably 80% or more. The upper limit of the surface ratio of the release agent is preferably 100%. When the surface ratio of the release agent is 70% or more, the low temperature fixability of the image can be improved.

[0089] Here, the method for measuring the surface layer ratio of the release agent is described.

[0090] The measurement samples and images were prepared by the following method.

[0091] The toner is mixed with the epoxy resin and embedded in the epoxy resin to cure the epoxy resin. The cured product is cut using an ultrathin sectioning device (Ultracut UCT manufactured by Leica Corporation) to form a thin sheet sample with a thickness of more than 80 nm and less than 130 nm. Then, an ultra-high resolution field emission scanning electron microscope (FE-SEM. S-4800 manufactured by Hitachi High-Technologies Corporation) is used to obtain an SEM image of the thin sheet sample. In the SEM image, a cross section of a toner particle having a maximum length of more than 85% of the volume average particle size of the toner particle is selected, and the domain of the release agent is observed to determine the area of ​​the release agent of the entire toner particle and the area of ​​the release agent present in the region within 800 nm from the surface of the toner particle, and calculate the area ratio of the two (the area of ​​the release agent present in the region within 800 nm from the surface of the toner particle / the area of ​​the release agent of the entire toner particle). Then, the calculation is performed on 100 toner particles, and the average value is used as the surface ratio of the release agent.

[0092] The reason for selecting a colorant particle cross section whose maximum length is greater than 85% of the volume average particle size of the colorant particle is that a cross section less than 85% of the volume average particle size is predicted to be a cross section at the end of the colorant particle, and the state of the domain in the colorant particle will not be well reflected in the cross section at the end of the colorant particle.

[0093] As a control method for making the surface layer ratio of the release agent 70% or more, for example, there is a method of making the toner particles have a core-shell structure and using a release agent when forming the shell.

[0094] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0095] As a release agent, for example, hydrocarbon wax is preferably used. Hydrocarbon wax is a wax having a hydrocarbon as a skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), microcrystalline wax, etc. Among them, as a hydrocarbon wax, from the viewpoint of fixability, for example, Fischer-Tropsch wax, polyethylene wax or polypropylene wax is preferred. And, for example, from the viewpoint of fixability, it is preferred that the toner particles contain a plurality of hydrocarbon waxes.

[0096] The ratio of the hydrocarbon wax to the total release agent is, for example, preferably 85 mass % or more, preferably 95 mass % or more, and more preferably 100 mass %.

[0097] The content of the release agent is, for example, preferably 1% by mass to 20% by mass, more preferably 3% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and even more preferably 5% by mass to 15% by mass, relative to the entire toner particles.

[0098] -Bonding resin-

[0099] As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, preferably 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.

[0100] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can use a crystalline polyester resin together with the amorphous polyester resin. However, the crystalline polyester resin is preferably used in a range of 2% by mass or more and 40% by mass or less (for example, more preferably 2% by mass or more and 20% by mass or less) relative to the entire binder resin.

[0101] The "crystallinity" of a resin refers to having a clear endothermic peak in differential scanning calorimetry (DSC) rather than a step-like change in endothermic value. Specifically, it means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0102] On the other hand, the "amorphous" nature of a resin means that the half width exceeds 10°C, the endothermic value shows a step-like change, or a clear endothermic peak cannot be confirmed.

[0103] Amorphous polyester resin

[0104] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, commercially available products or synthetic resins may be used as the non-crystalline polyester resin.

[0105] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.

[0106] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a crosslinked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.

[0107] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0108] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among them, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.

[0109] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylolpropane, and pentaerythritol.

[0110] The polyols may be used alone or in combination of two or more.

[0111] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 80° C. or lower, and more preferably 50° C. or higher and 65° C. or lower.

[0112] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K 7121-1987 "Determination of Transition Temperature of Plastics".

[0113] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0114] The number average molecular weight (Mn) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.

[0115] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0116] The weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement by GPC, GPC HLC-8120GPC manufactured by TOSOH CORPORATION is used as a measuring device, a TOSOH CORPORATION column TSKgel SuperHM-M (15 cm) is used, and THF solvent is used. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.

[0117] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.

[0118] In addition, when the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent can be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is removed by distillation. In the case of the presence of a monomer with poor compatibility in the copolymerization reaction, for example, the monomer with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomer, and then polycondensed together with the main component.

[0119] Crystalline polyester resin

[0120] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, as the crystalline polyester resin, a commercially available product may be used, and a synthetic resin may also be used.

[0121] Here, since the crystalline polyester resin easily forms a crystal structure, for example, it is preferable to use a polycondensate of a polymerizable monomer having a linear aliphatic group rather than a polycondensate of a polymerizable monomer having an aromatic group.

[0122] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0123] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 or more and 5 or less) alkyl esters.

[0124] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond can be used together with these dicarboxylic acids.

[0125] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0126] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadecanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol. Among them, examples of the aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0127] As the polyol, a trivalent or higher alcohol having a cross-linked structure or a branched structure may be used together with the diol. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0128] The polyols may be used alone or in combination of two or more.

[0129] Among them, the content of the polyol, for example, aliphatic diol is preferably 80 mol % or more, preferably 90 mol % or more.

[0130] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0131] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Determination of Transition Temperatures of Plastics".

[0132] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.

[0133] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a well-known production method.

[0134] Here, the binder resin may be used together with the polyester resin and other binder resins. As other binder resins, for example, styrene (meth) acrylic resins are preferably used.

[0135] -Styrene (meth) acrylic resin-

[0136] Styrene (meth) acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth) acryloyl group. "(Meth) acrylic" includes both "acrylic" and "methacrylic". Furthermore, "(meth) acryloyl" includes both "acryloyl" and "methacryloyl".

[0137] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more.

[0138] Among them, as the styrene-based monomer, for example, styrene is preferred from the viewpoint of reactivity, controllability of reaction, and availability.

[0139] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, and n-octadecyl (meth)acrylate). (meth)acrylate, such as pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, (meth)acrylamide, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.

[0140] The copolymerization ratio of the styrene-based monomer and the (meth)acrylic-based monomer (based on mass, styrene-based monomer / (meth)acrylic-based monomer) is preferably, for example, 85 / 15 to 70 / 30.

[0141] From the viewpoint of suppressing the print-through of the image, the styrene (meth) acrylic resin preferably has a cross-linked structure. Examples of the styrene (meth) acrylic resin having a cross-linked structure include a cross-linked product obtained by copolymerizing and cross-linking at least a monomer having a styrene skeleton, a monomer having a (meth) acrylic skeleton, and a cross-linking monomer.

[0142] Examples of the crosslinkable monomer include bifunctional or higher-functional crosslinking agents.

[0143] Examples of the bifunctional crosslinking agent include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, glycidyl(meth)acrylate, etc.), polyester di(meth)acrylate, and 2-([1'-methylpropyleneamino]carboxyamino)ethyl methacrylate.

[0144] Examples of the polyfunctional crosslinking agent include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diallyl chlorendonate, etc.

[0145] The copolymerization ratio of the crosslinkable monomer to all monomers (based on mass, crosslinkable monomer / all monomers) is preferably, for example, 2 / 1000 to 30 / 1000.

[0146] From the viewpoint of suppressing the strike-through of an image, the weight average molecular weight of the styrene (meth) acrylic resin is, for example, preferably 30,000 to 200,000, preferably 40,000 to 100,000, and more preferably 50,000 to 80,000.

[0147] The weight average molecular weight of the styrene (meth) acrylic resin is a value measured by the same method as the weight average molecular weight of the polyester resin.

[0148] From the viewpoint of balancing the fluidity and storage properties of the colorant and suppressing the print-through of the image, the content of the styrene (meth) acrylic resin is preferably, for example, 10% by mass or more and 30% by mass or less, preferably 12% by mass or more and 28% by mass or less, and more preferably 15% by mass or more and 25% by mass or less, relative to the colorant particles.

[0149] Furthermore, other binding resins may be used simultaneously as the binding resin.

[0150] As other binder resins, for example, there can be mentioned vinyl resins composed of homopolymers of monomers such as styrenes (for example, styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), vinyl ethers (for example, vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (for example, ethylene, propylene, butadiene, etc.), or copolymers formed by combining two or more of these monomers.

[0151] Other examples of binder resins include epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosins and other non-vinyl resins, mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers under the coexistence of the above-mentioned resins.

[0152] These other binder resins may be used alone or in combination of two or more.

[0153] The content of the binder resin is, for example, preferably 40 mass % to 95 mass % inclusive, more preferably 50 mass % to 90 mass % inclusive, and further preferably 60 mass % to 85 mass % inclusive, based on the entire toner particles.

[0154] -Colorants-

[0155] Examples of the colorant include various pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose Bengal, aniline blue, ultramarine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based.

[0156] The coloring agent may be used alone or in combination of two or more.

[0157] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant. Furthermore, a plurality of colorants may be used simultaneously.

[0158] The content of the colorant is, for example, preferably 1 mass % to 30 mass % inclusive, and more preferably 3 mass % to 15 mass % inclusive, based on the entire toner particles.

[0159] -Other additives-

[0160] Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.

[0161] -Characteristics of toner particles-

[0162] The toner particles may be toner particles of a single-layer structure, or toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) coating the core, and preferably a core-shell structure. The toner particles of a core-shell structure preferably consist of a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.

[0163] The volume average particle size (D50v) of the toner particles is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.

[0164] Various average particle diameters and various particle size distribution indices of the toner particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and those of the electrolyte were measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).

[0165] During measurement, 0.5 mg to 50 mg of a measurement sample is added as a dispersant to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate), and this is added to 100 ml to 150 ml of an electrolyte.

[0166] The electrolyte in which the sample was suspended was dispersed by an ultrasonic disperser for 1 minute, and the particle size distribution of particles with a particle size ranging from 2 μm to 60 μm was measured by Coulter Multisizer II using an aperture of 100 μm. The number of particles to be sampled was 50,000.

[0167] The cumulative distribution of volume and number is plotted for the particle size range (channel) divided based on the measured particle size distribution from the small diameter side, and the particle size when the cumulative amount reaches 16% is defined as the volume particle size D16v and the number average particle size D16p, the particle size when the cumulative amount reaches 50% is defined as the volume average particle size D50v and the number average particle size D50p, and the particle size when the cumulative amount reaches 84% ​​is defined as the volume particle size D84v and the number average particle size D84p.

[0168] Use them, by (D84v / D16v) 1 / 2 Calculate the volume average particle size distribution index (GSDv) from (D84p / D16p) 1 / 2 Calculate the number average particle size distribution index (GSDp).

[0169] The shape factor SF1 of the toner particles is, for example, preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.

[0170] The shape factor SF1 is obtained by the following formula.

[0171] Formula: SF1 = (ML 2 / A)×(π / 4)×100

[0172] In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of ​​the toner.

[0173] Specifically, the shape factor SF1 is digitized mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide is introduced into a Luzex image analyzer using a camera, the maximum length and projected area of ​​100 particles are obtained, and the calculation is performed using the above formula to obtain the average value.

[0174] -External Additives-

[0175] The toner may contain an external additive in addition to the toner particles.

[0176] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0177] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment, for example. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.

[0178] The amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0179] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin and other resin particles), cleaning aids (for example, metal salts of higher fatty acids represented by zinc stearate, and particles of fluorine-based high molecular weight bodies).

[0180] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.

[0181] -Method for producing toner-

[0182] The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles and, if the toner particles further contain an external additive, adding the external additive to the toner particles.

[0183] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation method, suspension polymerization method, dissolution suspension method, etc.). These methods are not particularly limited, and well-known methods can be used. Among them, it is preferred to obtain the toner particles by, for example, the aggregation method.

[0184] The following is a description of the details of each step of the aggregation method. In the following description, a method for obtaining toner particles containing a colorant is described, but a colorant can be used as needed. Of course, other additives besides the colorant can also be used.

[0185] ·Resin particle dispersion preparation process

[0186] First, a resin particle dispersion in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0187] The polyester resin particle dispersion is prepared by, for example, dispersing the polyester resin particles in a dispersion medium using a surfactant.

[0188] Examples of the dispersion medium used for the polyester resin particle dispersion include aqueous media.

[0189] Examples of the aqueous medium include water such as distilled water and deionized water; and alcohols, etc. These may be used alone or in combination of two or more.

[0190] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among them, anionic surfactants and cationic surfactants are particularly useful. Nonionic surfactants may be used together with anionic surfactants or cationic surfactants.

[0191] The surfactant may be used alone or in combination of two or more.

[0192] As a method for dispersing polyester resin particles in a dispersion medium, for example, conventional dispersion methods using a rotary shearing homogenizer or a ball mill, sand mill, DYNO-MILL, etc. with a medium can be cited. In addition, the polyester resin particles can also be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method refers to the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (0 phase) for neutralization, and then water (W phase) is added to perform a phase inversion from W / 0 to 0 / W, thereby dispersing the resin in the aqueous medium into particles.

[0193] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably 0.01 μm to 1 μm, more preferably 0.08 μm to 0.8 μm, and further preferably 0.1 μm to 0.6 μm.

[0194] The volume average particle size of the polyester resin particles is obtained by measuring the particle size distribution obtained by a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by HORIBA, Ltd.) by plotting the cumulative distribution of the volume in the particle size range (channel) divided from the small particle size side, and the particle size when the cumulative amount reaches 50% relative to all particles is taken as the volume average particle size D50v. In addition, the volume average particle size of particles in other dispersions is measured in the same manner.

[0195] The content of the polyester resin particles contained in the polyester resin particle dispersion is, for example, preferably 5 mass % or more and 50 mass % or less, and more preferably 10 mass % or more and 40 mass % or less.

[0196] Similar to the polyester resin particle dispersion, a colorant dispersion and a release agent particle dispersion are also prepared. That is, the dispersion medium, dispersion method, volume average particle size of the particles, and particle content in the polyester resin particle dispersion are also the same in the colorant dispersion and the release agent particle dispersion.

[0197] ·First agglomerated particle forming step

[0198] Next, the polyester resin particle dispersion and the colorant dispersion are mixed.

[0199] Then, the polyester resin particles and the colorant particles are heterogeneously aggregated in the mixed dispersion to form first aggregated particles having a diameter close to the target diameter of the toner particles and containing the polyester resin particles and the colorant particles.

[0200] Furthermore, if necessary, the first aggregated particles may be mixed with a release agent particle dispersion so as to contain the release agent particles.

[0201] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, pH 2 or more and pH 5 or less), and after a dispersion stabilizer is added as needed, it is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, -30°C or more and -10°C or less of the glass transition temperature of the polyester resin) to aggregate the particles dispersed in the mixed dispersion to form first aggregated particles.

[0202] In the first agglomerated particle formation step, for example, the mixed dispersion can be stirred using a rotary shearing homogenizer, a coagulant can be added at room temperature (e.g., 25° C.), the pH of the mixed dispersion can be adjusted to acidic (e.g., pH 2 or more and pH 5 or less), a dispersion stabilizer can be added as needed, and then heating can be performed.

[0203] Examples of the coagulant include surfactants having polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of the coagulant used can be reduced, thereby improving the charging characteristics.

[0204] An additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As such an additive, a chelating agent may be used.

[0205] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0206] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0207] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.

[0208] · Second aggregated particle forming step

[0209] After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance and then the mixed solution may be mixed into the first aggregated particle dispersion.

[0210] Then, in the mixed dispersion in which the first aggregated particles, the polyester resin particles, and the release agent particles are dispersed, the polyester resin particles and the release agent particles are aggregated so that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.

[0211] Specifically, for example, in the first aggregated particle forming step, when the first aggregated particles reach the target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed with the first aggregated particle dispersion. Next, the mixed dispersion is heated at a temperature below the glass transition temperature of the polyester resin, the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5, and aggregation is stopped.

[0212] Thus, second aggregated particles are obtained in which the polyester resin particles and the release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles.

[0213] Melting / combination process

[0214] Next, the second aggregated particle dispersion containing the second aggregated particles is heated, for example, to a temperature above the glass transition temperature of the polyester resin (for example, a temperature 10°C to 50°C higher than the glass transition temperature of the polyester resin) to melt / combine the second aggregated particles to form toner particles.

[0215] Through the above steps, toner particles are obtained.

[0216] In addition, the colorant particles can also be manufactured through the following steps: after obtaining the second agglomerated particle dispersion in which the second agglomerated particles are dispersed, further mixing the second agglomerated particle dispersion and the polyester resin particle dispersion in which the polyester resin particles are dispersed to agglomerate the polyester resin particles so as to further adhere to the surface of the second agglomerated particles to form third agglomerated particles; and heating the third agglomerated particle dispersion in which the third agglomerated particles are dispersed to melt / combine the third agglomerated particles to form colorant particles.

[0217] After the melting / combining step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.

[0218] The washing process is not particularly limited, but from the viewpoint of chargeability, it is preferred to fully perform replacement washing with deionized water. In addition, the solid-liquid separation process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform suction filtration, pressure filtration, etc. In addition, the method of the drying process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform freeze drying, airflow drying, fluidized drying, vibration-type fluidized drying, etc.

[0219] The toner according to the present embodiment is produced by, for example, adding an external additive to dry toner particles and mixing them. The mixing is preferably performed by, for example, a V mixer, a Henschel mixer, a Lödige mixer, etc. Furthermore, coarse particles of the toner may be removed by using a vibration sieving machine, a wind sieving machine, etc. as needed.

[0220] - Electrostatic latent image developer -

[0221] In this embodiment, the electrostatic latent image developer contained in the developing member contains at least the above-mentioned toner. The electrostatic latent image developer may be a single-component developer containing only the toner, or a two-component developer in which the toner and a carrier are mixed.

[0222] The carrier is not particularly limited, and known carriers can be cited. Examples of the carrier include a coated carrier in which the surface of a core material containing magnetic powder is coated with a resin; a magnetic powder dispersed carrier prepared by dispersing magnetic powder in a matrix resin; and a resin impregnated carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersed carrier and the resin impregnated carrier can be a carrier in which the constituent particles of the carrier are used as a core material and the surface is coated with a resin.

[0223] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.

[0224] Examples of the conductive particles include particles of metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0225] Examples of the coating resin and the matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, linear silicone resin containing an organic siloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and the matrix resin may contain additives such as a conductive material.

[0226] The method of coating the surface of the core material with a resin includes a method of coating with a coating layer forming solution obtained by dissolving a coating resin and various additives (used as needed) in an appropriate solvent. The solvent is not particularly limited, and can be selected by considering the type of resin used and coating suitability. Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution; a spraying method in which the coating layer forming solution is sprayed on the surface of the core material; a fluidized bed method in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and then the solvent is removed.

[0227] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100.

[0228] (Cleaning scraper)

[0229] A cleaning blade used in the image forming apparatus according to the present embodiment is described. The cleaning blade has a double-layer structure consisting of an edge layer and a back layer, and the edge layer and the back layer are made of polyurethane resin. The ratio (Hb / Ha) of the hardness Hb of the edge layer of the cleaning blade to the hardness Ha of the back layer is 0.84 or more and 0.93 or less. Furthermore, the total amount of F and Si present within 200 nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.

[0230] -Ratio (Hb / Ha)-

[0231] The ratio (Hb / Ha) of the hardness Hb of the edge layer of the cleaning blade to the hardness Ha of the back layer is 0.84 or more and 0.93 or less. When the ratio (Hb / Ha) is within the above range, the followability of the cleaning blade to the opposing surface can be improved, thereby suppressing the generation of staple marks on the formed image. Furthermore, the ratio (Hb / Ha) is preferably 0.87 or more and 0.90 or less, and more preferably 0.88 or more and 0.89 or less.

[0232] - Hardness of edge layer and back layer -

[0233] The hardness Ha of the back layer is preferably 85° or more and 95° or less, more preferably 87° or more and 93° or less, and further preferably 89° or more and 91° or less. When the hardness of the back layer is 85° or more, the occurrence of lifting on the cleaning blade can be suppressed. When the hardness of the back layer is 95° or less, the followability of the cleaning blade to follow the opposing surface can be further improved.

[0234] The hardness Hb of the edge layer is preferably 75° or more and less than 85°, more preferably 77° or more and 83° or less, and further preferably 79° or more and 81° or less. When the hardness of the edge layer is 75° or more, excellent cleaning performance can be achieved, and the wear of the cleaning blade can be suppressed. When the hardness of the edge layer is less than 85°, the followability of the cleaning blade to follow the opposing surface can be further improved.

[0235] In addition, the hardness of each layer in the cleaning blade was measured by the following method.

[0236] The hardness was measured according to the hardness test method shown in JIS K6253 (1997) using a type A hardness meter specified in JIS K7215 (1986). Specifically, a type A hardness meter (manufactured by KOBUNSHI KEIKI CO., LTD.) specified in JIS K7215 (1986) was used to press the indenter (indenter) on the contact portion, and the maximum value of the pointer was read within 1 second. Then, this measurement was repeated 5 times, and the JIS-A hardness of the contact portion was calculated from the average value.

[0237] When the contact portion of the edge layer of the cleaning blade is subjected to a modification process described below, the position subjected to the modification process is the object of the hardness measurement. However, it is considered that the hardness of the position subjected to the modification process described below and the position not subjected to the modification process are almost the same.

[0238] -Surface ratio of F and Si-

[0239] In the cleaning blade, the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the edge layer in contact with the intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si) is 75% or more. When the surface ratio of F and Si at the contact portion of the cleaning blade is 75% or more, the state of the front end of the contact portion of the cleaning blade becomes stable, thereby suppressing the occurrence of toner filming on the surface of the intermediate transfer belt. Furthermore, the surface ratio of F and Si at the contact portion of the cleaning blade is preferably 85% or more, and more preferably 90% or more, for example.

[0240] -Surface F and Si content-

[0241] In the cleaning blade, the total amount of F and Si (surface F and Si amount) present on the surface (contact portion) of the edge layer in contact with the intermediate transfer belt is, for example, preferably 15 atm% or more, more preferably 18 atm% or more, and further preferably 20 atm% or more. When the surface F and Si amount at the contact portion of the cleaning blade is 15 atm% or more, the state of the front end of the contact portion of the cleaning blade becomes more stable, thereby further suppressing the toner filming on the surface of the intermediate transfer belt.

[0242] In addition, the upper limit of the surface F and Si amount at the contact portion of the cleaning scraper is not particularly limited, but from the viewpoint of suppressing poor cleaning (the viscosity of the front end portion becomes insufficient due to the decrease in the friction coefficient, resulting in a state of contact in the middle portion, which leads to poor cleaning), it is preferably less than 25 atm%, and more preferably less than 22 atm%.

[0243] -50nm position F and Si amount-

[0244] In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface (contact portion) of the edge layer in contact with the intermediate transfer belt (the amount of F and Si at the 50 nm position) is, for example, preferably 0.3 atm% or more, more preferably 0.5 atm% or more, and further preferably 1.0 atm% or more. When the amount of F and Si at the 50 nm position of the cleaning blade is 0.3 atm% or more, the friction at the contact portion of the cleaning blade is continuously reduced, thereby suppressing the toner filming on the surface of the intermediate transfer belt over time.

[0245] The upper limits of the 50 nm position F and the Si amount of the cleaning blade are not particularly limited, but are preferably 7 atm % or less, and more preferably 5 atm % or less, from the viewpoint of suppressing local wear.

[0246] In a cleaning blade, a method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the edge layer in contact with the intermediate transfer belt to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si) is described. That is, a method for analyzing the amount of F and the amount of Si in the depth direction from the contact portion of the edge layer of the cleaning blade is described.

[0247] The area including the surface (contact portion) of the cleaning blade edge layer in contact with the intermediate transfer belt was cut out, and the amounts (atm %) of N, C, O, F and Si elements were measured from the contact portion toward the depth direction using XPS (Versa Probe II manufactured by ULVAC-PHI, Inc.).

[0248] Furthermore, the total amount of F and Si present on the surface (contact portion) of the edge layer in contact with the intermediate transfer belt in the cleaning blade was determined as follows: for the plot of the depth from the contact portion of the cleaning blade obtained by the above-mentioned analysis in the depth direction and the element ratio, the area to a depth of 5 μm was set as SA, and the area to a depth of 200 nm was set as SB, and the ratio was calculated according to the formula SB / SA×100. In addition, the total amount of F and Si present at a position 50 nm from the surface (contact portion) of the edge layer in contact with the intermediate transfer belt in the cleaning blade was similarly determined.

[0249] -structure-

[0250] In this embodiment, a cleaning blade having a double-layer structure of an edge layer and a back layer is used, that is, a cleaning blade having an edge layer including a contact portion with the intermediate transfer belt and a back layer formed on the back side of the edge layer and made of a material different from that of the edge layer is used.

[0251] The edge layer and the back layer of the cleaning blade are both made of polyurethane resin.

[0252] Polyurethane resin

[0253] The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. The polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group that can react with an isocyanate group of a polyisocyanate in addition to the polyol component as needed.

[0254] For example, the polyurethane resin preferably has a hard segment and a soft segment. The "hard segment" and the "soft segment" refer to segments in which the material constituting the former is composed of a relatively harder material than the material constituting the latter, and the material constituting the latter is composed of a relatively softer material than the material constituting the former.

[0255] In addition, as the material constituting the hard segment (hard segment material), there can be mentioned a low molecular weight polyol component among the polyol components, a resin having a functional group capable of reacting with an isocyanate group of a polyisocyanate, etc. On the other hand, as the material constituting the soft segment (soft segment material), there can be mentioned a high molecular weight polyol component among the polyol components.

[0256] Here, the average particle size of the aggregates of the hard segments is, for example, preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less.

[0257] By setting the average particle size of the hard segment aggregates to 1 μm or more, the frictional resistance on the contact member surface is easily reduced. Therefore, the blade behavior becomes stable and local wear is easily suppressed.

[0258] On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping can be easily suppressed.

[0259] The average particle size of the hard segment aggregates was measured as follows: an image was captured at a magnification of ×20 using a polarizing microscope (BX51-P manufactured by Olympus Corporation), the image was processed to binarize the image, 5 points were measured on each cleaning blade (the particle size of 5 aggregates was measured at each point), the particle size (equivalent circle diameter) of the aggregates was measured for 20 cleaning blades, and the average particle size was calculated from a total of 500.

[0260] The image was binarized using image processing software OLYMPUS Stream essentials (manufactured by Olympus Corporation) to adjust the thresholds of hue / chroma / brightness so that the crystal part and the hard segment aggregates were black and the amorphous part (equivalent to the soft segment) was white.

[0261] Polyol ingredients

[0262] The polyol component includes high molecular weight polyols and low molecular weight polyols.

[0263] The high molecular weight polyol component is a polyol having a number average molecular weight of 500 or more (e.g., preferably 500 or more and 5000 or less). As the high molecular weight polyol component, polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, polyether polyols and other well-known polyols can be cited. In addition, as commercially available products of high molecular weight polyols, for example, PLAXEL205 or PLAXEL240 manufactured by Daicel Corporation can be cited.

[0264] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same shall apply hereinafter.

[0265] These high molecular weight polyols may be used alone or in combination of two or more.

[0266] The polymerization ratio of the high molecular weight polyol component is preferably, for example, 30 mol % or more and 50 mol % or less, and preferably 40 mol % or more and 50 mol % or less, based on all the polymerization components of the polyurethane resin.

[0267] The low-molecular-weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low-molecular-weight polyol is a material that functions as a chain extender and a cross-linking agent.

[0268] Examples of the low molecular weight polyol component include 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol. Among them, 1,4-butanediol is preferably used as the low molecular weight polyol component.

[0269] Examples of the low molecular weight polyol component include diol (bifunctional), triol (trifunctional) and tetraol (tetrafunctional) which are well known as chain extenders and crosslinking agents.

[0270] These polyols may be used alone or in combination of two or more.

[0271] The polymerization ratio of the low molecular weight polyol relative to all the polymerization components of the polyurethane resin is preferably greater than 50 mol% and less than 75 mol%, preferably greater than 52 mol% and less than 75 mol%, more preferably greater than 55 mol% and less than 75 mol%, and further preferably greater than 55 mol% and less than 60 mol%.

[0272] Polyisocyanate ingredients

[0273] Examples of the polyisocyanate component include 4,4-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexane diisocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3′-dimethylbiphenyl-4,4′-diisocyanate (TODI).

[0274] As the polyisocyanate component, for example, 4,4′-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.

[0275] These polyisocyanate components may be used alone or in combination of two or more.

[0276] The polymerization ratio of the polyisocyanate component is preferably, for example, 5 mol % or more and 25 mol % or less, and preferably 10 mol % or more and 20 mol % or less, based on all the polymerization components of the polyurethane resin.

[0277] Resins having functional groups capable of reacting with isocyanate groups

[0278] The resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, an aliphatic resin having a linear structure is more preferred. Specific examples of the functional group-containing resin include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins having two or more epoxy groups.

[0279] Examples of commercially available products of acrylic resins containing two or more hydroxyl groups include ACTFLOW manufactured by Soken Chemical & Engineering Co., Ltd. (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.).

[0280] Examples of commercially available products of the polybutadiene resin containing two or more hydroxyl groups include R-45HT manufactured by IDEMITSU LUBE.

[0281] As the epoxy resin having two or more epoxy groups, for example, an epoxy resin having a hard and brittle property as conventional general epoxy resins is not preferred, and an epoxy resin having a softer and tougher property than conventional epoxy resins is preferred. As the above-mentioned epoxy resin, for example, from the viewpoint of molecular structure, an epoxy resin having a structure (flexible skeleton) capable of improving the mobility of the main chain in its main chain structure is preferred, and as the flexible skeleton, for example, an alkylene skeleton, a cycloalkane skeleton, a polyoxyalkylene skeleton, etc. can be cited, and a polyoxyalkylene skeleton is particularly preferred.

[0282] Furthermore, from the viewpoint of physical properties, epoxy resins having a lower viscosity than the molecular weight are preferred compared to existing epoxy resins. Specifically, for example, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins having such properties include, for example, EPICLON EXA-4850-150 manufactured by DIC CORPORATION.

[0283] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the characteristics of the cleaning blade, for example.

[0284] ·Production method of polyurethane resin

[0285] The polyurethane resin can be produced by a conventional polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent wear resistance and chipping resistance, but the method is not limited thereto.

[0286] The cleaning blade is produced by forming the cleaning blade-forming composition prepared by the above method into a sheet by centrifugal molding, extrusion molding, or the like, and then cutting the sheet.

[0287] Here, examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, quaternary ammonium salts, and organometallic compounds such as organotin compounds.

[0288] Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, amino alcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, esteramines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.

[0289] Examples of the quaternary ammonium salt include 2-hydroxypropyltrimethylammonium-octylate, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octylate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formatate, and 2-hydroxypropyltrimethylammonium-formatate.

[0290] Examples of the organic tin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexanoate), stannous 2-ethylhexanoate, and stannous oleate.

[0291] Among these catalysts, triethylenediamine (TEDA) which is a tertiary ammonium salt is used from the viewpoint of hydrolysis resistance, and quaternary ammonium salts are used from the viewpoint of processability. Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octanoate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octanoate, and DBU-formate which have high reactivity are used.

[0292] The content of the catalyst is, for example, preferably in the range of 0.0005% by mass or more and 0.03% by mass or less, and particularly preferably 0.001% by mass or more and 0.01% by mass or less, based on the entire polyurethane resin constituting the contact member.

[0293] These are used alone or in combination of two or more.

[0294] ·Manufacturing of double-layer cleaning scraper

[0295] The edge layer and the back layer are integrally formed by a centrifugal forming method. First, the molten material of the back layer is injected into a centrifugal forming drum, and the centrifugal forming drum is rotated. As a result, the material of the back layer is evenly spread on the inner circumference of the centrifugal forming drum and gradually solidifies. Then, before the material of the back layer is completely solidified (while the material is viscous), the molten material of the edge layer is injected into the centrifugal forming drum, and the material is solidified while the centrifugal forming drum is rotated. Then, the solidified material is taken out from the centrifugal forming drum and a cleaning blade is cut out.

[0296] Furthermore, the cleaning blade having a double-layer structure of an edge layer and a back layer can also be produced by separately producing an edge layer and a back layer by the above-mentioned method for producing a polyurethane resin, and laminating the obtained edge layer and back layer.

[0297] In addition, as a method for making the hardness of the edge layer and the back layer different, a method of changing the material of the polyurethane resin, for example, a method of changing the ratio of the hard segment to the soft block can be mentioned.

[0298] Modification of contact parts

[0299] In this embodiment, since the ratio of the total amount of F and Si present within 200nm from the surface (contact portion) of the edge layer in contact with the intermediate transfer belt in the cleaning scraper to the total amount of F and Si present within 5μm from the surface (surface ratio of F and Si) is set within the above-mentioned range, it is preferred, for example, to allow at least one of the F element and the Si element to penetrate into the contact portion of the edge layer of the obtained cleaning scraper, thereby having a modified layer that has been subjected to surface modification treatment.

[0300] The modified layer is a layer obtained by impregnating a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of F element and Si element, and an organic solvent into the contact portion of the cleaning blade and curing the surface treatment liquid (ie, the isocyanate compound and the specific polymer).

[0301] The modified layer is formed integrally with the surface layer of the contact portion so as to gradually become sparse from the surface toward the inside.

[0302] Examples of the isocyanate compound include 2,6-toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), p-phenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethylbiphenyl-4,4'-diisocyanate (TODI), and polymers thereof and modified products thereof. In addition, examples of modified products of the isocyanate compound include urethane prepolymers obtained by prepolymerizing an isocyanate compound with a polyol.

[0303] The specific polymer is preferably a compound that is soluble in a predetermined solvent and reacts with an isocyanate compound to chemically bond therewith. Examples of acrylic polymers having a siloxane bond include block copolymers of (meth)acrylate and (meth)siloxane acrylate and derivatives thereof. In addition, "(meth)acrylic acid" means either or both of acrylic acid and methacrylic acid.

[0304] Examples of the acrylic polymer having a fluorine atom include a block copolymer of (meth)acrylic acid ester and fluoroalkyl methacrylate and a derivative thereof.

[0305] For example, the cleaning blade preferably contains a polymer having a siloxane bond (silicone-based polymer) at a portion in contact with the intermediate transfer belt.

[0306] Furthermore, from the viewpoint of solubility in an organic solvent, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group, for example.

[0307] In addition, as a method for confirming that the surface layer of the contact portion of the cleaning blade contains a specific polymer and a method for confirming that the surface layer contains a specific polymer that is an acrylic polymer, for example, the following method can be cited. Specifically, the confirmation is as follows: the structure estimation or composition analysis of the surface layer material of the contact portion of the cleaning blade is performed by an analysis method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).

[0308] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass to 13 parts by mass, preferably 9 parts by mass to 13 parts by mass, and more preferably 10 parts by mass to 13 parts by mass, relative to 100 parts by mass of the isocyanate compound.

[0309] The organic solvent is preferably a solvent that dissolves the specific polymer and is compatible with the isocyanate compound, and specifically includes ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, as the organic solvent, a reactive diluent such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, trimethylolpropane triacrylate, etc. can be used.

[0310] The modified layer is formed, for example, by impregnating and applying the surface treatment liquid to at least the contact portion of the cleaning blade, removing the organic solvent by drying, and forming a cured layer by heat treatment.

[0311] The impregnation coating method is not particularly limited, and examples thereof include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the impregnation coating method, the impregnation time may be, for example, in the range of 10 seconds to 60 seconds.

[0312] Drying conditions after impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 minute to 10 minutes. Heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 minutes to 90 minutes.

[0313] Pressing force

[0314] The pressing force NF (Normal Force) of the cleaning blade against the intermediate transfer belt is preferably, for example, 1.5 gf / mm or more and 3.5 gf / mm or less, and more preferably 2.0 gf / mm or more and 3.2 gf / mm or less. When the pressing force NF is 1.5 gf / mm or more, the occurrence of staple marks on the image can be further suppressed, and when the pressing force NF is 3.5 gf / mm or less, the occurrence of toner filming on the surface of the intermediate transfer belt can be further suppressed.

[0315] Here, the pressing force NF of the cleaning blade is calculated by the following formula.

[0316] Formula: Pressing force NF = k × d

[0317] Where k represents the spring constant inherent to the cleaning blade, and d represents the amount of penetration of the cleaning blade into the intermediate transfer belt (reference Figure 2 ).

[0318] The spring constant k inherent to the cleaning blade is obtained by displacing the cleaning blade 12 and measuring the load with a load cell.

[0319] Regarding the biting amount d of the cleaning blade with respect to the intermediate transfer belt, the cleaning blade 12 was fixed to a supporting member and the displacement amount of the cleaning blade when it was brought into contact with the intermediate transfer belt was calculated.

[0320] Here, in Figure 2 In the figure, BE denotes an intermediate transfer belt, CB denotes a cleaning blade, and CBS denotes a supporting member that supports the cleaning blade.

[0321] The amount of bite d of the cleaning blade into the intermediate transfer belt is, for example, preferably not less than 0 mm and not more than 10 mm, and more preferably not less than 0.01 mm and not more than 5 mm.

[0322] (Intermediate transfer belt and transfer device)

[0323] -Layer structure of intermediate transfer belt-

[0324] Examples of the intermediate transfer belt include a single-layer body of a polyimide-based resin layer and a laminated body having a polyimide-based resin layer as an outermost layer.

[0325] It is preferable that the outer peripheral surface of the intermediate transfer belt is formed of, for example, a polyimide-based resin layer.

[0326] When the intermediate transfer belt is composed of a laminate having a polyimide resin layer as the outermost layer, an intermediate transfer belt having a polyimide resin layer disposed on a resin substrate layer is used. Alternatively, an intermediate layer (elastic layer, etc.) may be disposed between the substrate layer and the polyimide resin layer.

[0327] As the resin base material layer and the intermediate layer (elastic layer, etc.), known layers used in the intermediate transfer belt can be applied.

[0328] [Structure of polyimide resin layer]

[0329] The polyimide resin layer contains, for example, a polyimide resin and conductive carbon particles. The polyimide resin layer preferably contains, for example, a release agent.

[0330] Furthermore, the polyimide-based resin layer may contain other well-known components as necessary.

[0331] Here, the polyimide-based resin layer refers to a layer having the largest content of the polyimide-based resin by mass among the resin layer constituent components.

[0332] -Polyimide resin-

[0333] The polyimide-based resin refers to a resin containing a structural unit having an imide bond.

[0334] Examples of the polyimide-based resin include polyimide resins, polyamide-imide resins, and polyether-imide resins.

[0335] Among them, from the viewpoint of cleanliness maintenance performance, as the polyimide-based resin, for example, a polyimide resin and a polyamide-imide resin are preferred, and a polyimide resin is more preferred.

[0336] As a polyimide resin, the imidation product of the polyamic acid (precursor of a polyimide resin) which is a polymer of a tetracarboxylic dianhydride and a diamine compound is mentioned, for example.

[0337] Examples of the polyimide resin include resins having a structural unit represented by the following general formula (I).

[0338] [Chemical formula 1]

[0339]

[0340] In the general formula (I), R 1 represents a tetravalent organic group, R 2 It represents a divalent organic group.

[0341] As R 1 The tetravalent organic group represented by the present invention includes an aromatic group, an aliphatic group, a cyclic aliphatic group, a group formed by combining an aromatic group and an aliphatic group, or a substituted group thereof. Specifically, the tetravalent organic group includes, for example, a residue of tetracarboxylic dianhydride described below.

[0342] As R 2 The divalent organic group represented by the compound may be an aromatic group, an aliphatic group, a cyclic aliphatic group, a group formed by combining an aromatic group and an aliphatic group, or a substituted group thereof. Specifically, the divalent organic group may be a residue of a diamine compound described below.

[0343] Specific examples of the tetracarboxylic dianhydride used as a raw material for the polyimide resin include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)sulfonic acid dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, and ethylenetetracarboxylic dianhydride.

[0344] Specific examples of the diamine compound used as a raw material of the polyimide resin include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, m-phenylenediamine, p-phenylenediamine, 3,3'-dimethyl-4,4'-biphenylenediamine, benzidine, 3,3'-dimethyl Benzidine, 3,3'-dimethoxybenzidine, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl propane, 2,4-bis(amino tert-butyl)toluene, bis(p-β-amino tert-butylphenyl) ether, bis(p-β-methyl-δ-aminophenyl)benzene, bis-p-(1,1-dimethyl-5-aminopentyl)benzene, 1-isopropyl-2,4-m-phenylenediamine, m-phenylenediamine, p-phenylenediamine, di(p-aminocyclohexyl)methane, hexadecene Methylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, diaminopropyltetramethylene, 3-methylheptamethylenediamine, 4,4-dimethylheptamethylenediamine, 2,11-diaminododecane, 1,2-bis-3-aminopropoxyethane, 2,2-dimethylpropylenediamine, 3-methoxyhexamethylenediamine, 2,5-dimethylheptamethylenediamine, 3-methylheptamethylenediamine, 5-methylnonamethylenediamine Amine, 2,17-diaminoeicosane, 1,4-diaminocyclohexane, 1,10-diamino-1,10-dimethyldecane, 12-diaminooctadecane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, piperazine, H2N(CH2)3O(CH2)2O(CH2)NH2, H2N(CH2)3S(CH2)3NH2, H2N(CH2)3N(CH3)2(CH2)3NH2, etc.

[0345] Examples of the polyamide-imide resin include resins having an imide bond and an amide bond in a repeating unit.

[0346] More specifically, examples of the polyamide-imide resin include polymers of a trivalent carboxylic acid compound (also referred to as tricarboxylic acid) having an acid anhydride group and a diisocyanate compound or a diamine compound.

[0347] As the tricarboxylic acid, for example, trimellitic anhydride and its derivatives are preferred. In addition to the tricarboxylic acid, tetracarboxylic dianhydride, aliphatic dicarboxylic acid, aromatic dicarboxylic acid, etc. may be used simultaneously.

[0348] Examples of the diisocyanate compound include 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 2,2'-dimethylbiphenyl-4,4'-diisocyanate, biphenyl-4,4'-diisocyanate, biphenyl-3,3'-diisocyanate, biphenyl-3,4'-diisocyanate, 3,3'-diethylbiphenyl-4,4'-diisocyanate, 2,2'-diethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, 2,2'-dimethoxybiphenyl-4,4'-diisocyanate, naphthalene-1,5-diisocyanate, and naphthalene-2,6-diisocyanate.

[0349] Examples of the diamine compound include compounds having the same structure as the above-mentioned isocyanate and having an amino group instead of an isocyanate group.

[0350] From the viewpoint of mechanical strength and volume resistivity adjustment, the content of the polyimide resin relative to the polyimide resin layer is, for example, preferably 60 mass % or more and 95 mass % or less, more preferably 70 mass % or more and 95 mass % or less, and further preferably 75 mass % or more and 90 mass % or less.

[0351] -Conductive carbon particles-

[0352] Examples of the conductive carbon particles include carbon black.

[0353] Examples of carbon black include Ketjen black, oil furnace black, channel black, acetylene black, etc. As carbon black, surface-treated carbon black (hereinafter also referred to as "surface-treated carbon black") can be used.

[0354] Surface-treated carbon black is obtained, for example, by imparting a carboxyl group, a quinone group, a lactone group, a hydroxyl group, etc. to its surface. Examples of surface treatment methods include an air oxidation method in which the carbon black is contacted with air in a high-temperature atmosphere to react, a method in which the carbon black is reacted with nitrogen oxides or ozone at room temperature (e.g., 22° C.), a method in which the carbon black is oxidized with air in a high-temperature atmosphere and then oxidized with ozone at a low temperature, and the like.

[0355] From the viewpoints of dispersibility, mechanical strength, volume resistivity, film-forming properties, etc., the average particle size of the conductive carbon particles is, for example, preferably from 2 nm to 40 nm, more preferably from 8 nm to 20 nm, and further preferably from 10 nm to 15 nm.

[0356] The average particle size of the conductive carbon particles is measured by the following method.

[0357] First, a 100 nm thick sample was collected from the polyimide resin layer using a microtome, and the sample was observed using a TEM (transmission electron microscope). Then, the diameter of a circle equal to the projected area of ​​each of 50 conductive carbon particles (i.e., equivalent circle diameter) was taken as the particle size, and the average value thereof was taken as the average particle size.

[0358] From the viewpoint of mechanical strength and volume resistivity, the content of the conductive carbon particles is preferably, for example, 10% by mass or more and 50% by mass or less relative to the polyimide-based resin layer.

[0359] -Other ingredients-

[0360] Examples of other components include conductive agents other than conductive carbon particles, fillers for improving mechanical strength, antioxidants for preventing thermal degradation of the tape, surfactants for improving fluidity, heat-resistant antioxidants, and release agents.

[0361] When other components are contained, the content of other components is, for example, preferably more than 0 mass % and 10 mass % or less, more preferably more than 0 mass % and 5 mass % or less, and further preferably more than 0 mass % and 1 mass % or less, relative to the polyimide resin layer.

[0362] ·Thickness of polyimide resin layer

[0363] When the intermediate transfer belt is composed of a single-layer body of a polyimide-based resin layer, the thickness of the polyimide-based resin layer is, for example, preferably 60 μm to 120 μm, and more preferably 80 μm to 120 μm, from the viewpoint of mechanical strength.

[0364] When the intermediate transfer belt is composed of a laminate having a polyimide resin layer as the outermost layer, the thickness of the polyimide resin layer is, for example, preferably greater than 1 μm and less than 60 μm, more preferably greater than 3 μm and less than 60 μm, from the viewpoint of manufacturing adaptability and discharge suppression.

[0365] In addition, the thickness of the polyimide-based resin layer was measured as follows.

[0366] Specifically, a cross section of the polyimide resin layer in the thickness direction is observed with an optical microscope or a scanning electron microscope, the thickness of the layer to be measured is measured at 10 locations, and the average value is defined as the thickness.

[0367] Volume resistivity of the intermediate transfer belt

[0368] From the viewpoint of transferability, the common logarithm of the volume resistivity of the intermediate transfer belt when a voltage of 500 V is applied for 10 seconds is, for example, preferably greater than 9.0 (logΩ·cm) and less than 13.5 (logΩ·cm), more preferably greater than 9.5 (logΩ·cm) and less than 13.2 (logΩ·cm), and particularly preferably greater than 10.0 (logΩ·cm) and less than 12.5 (logΩ·cm).

[0369] The volume resistivity of the intermediate transfer belt when a voltage of 500 V was applied for 10 seconds was measured by the following method.

[0370] As a resistance measuring machine, a microammeter (R8430A manufactured by ADVANTEST CORPORATION) was used, and as a probe, a UR probe (manufactured by Nittoseiko Analytech Co., Ltd.) was used. With respect to the volume resistivity (logΩ·cm), the intermediate transfer belt was measured at 6 locations at equal intervals in the circumferential direction, and at 3 locations in the center and both ends in the width direction, under the conditions of a voltage of 500 V, an application time of 10 seconds, and a pressure of 1 kgf, for a total of 18 locations, and the average value was calculated. The measurement was performed in an environment of a temperature of 22° C. and a humidity of 55% RH.

[0371] Surface resistivity of the intermediate transfer belt

[0372] From the viewpoint of transferability onto embossed paper, the common logarithm value of the surface resistivity of the intermediate transfer belt when a voltage of 500 V is applied to the outer surface for 10 seconds is, for example, preferably from 10.0 (logΩ / suq.) to 15.0 (logΩ / suq.), more preferably from 10.5 (logΩ / suq.) to 14.0 (logΩ / suq.), and particularly preferably from 11.0 (logΩ / suq.) to 13.5 (logΩ / suq.).

[0373] The unit of the surface resistivity, logΩ / suq., is a unit expressing the surface resistivity by the logarithmic value of the resistance value per unit area, and is also expressed as log(Ω / suq.), logΩ / suquare, logΩ / □, and the like.

[0374] The surface resistivity of the outer peripheral surface of the intermediate transfer belt when a voltage of 500 V was applied for 10 seconds was measured by the following method.

[0375] As a resistance measuring machine, a micro ammeter (R8430A manufactured by ADVANTEST CORPORATION) was used, and as a probe, a UR probe (manufactured by Nittoseiko Analytech Co., Ltd.) was used. The surface resistivity (logΩ / suq.) of the outer peripheral surface of the intermediate transfer belt was measured at 6 locations at equal intervals in the circumferential direction, and at 3 locations in the center and both ends in the width direction, for a total of 18 locations, and the average value was calculated. The measurement was performed in an environment of a temperature of 22° C. and a humidity of 55% RH.

[0376] - Primary transfer device -

[0377] In the primary transfer device, the primary transfer member is disposed opposite to the image holder with the intermediate transfer belt interposed therebetween. In the primary transfer device, the toner image is primarily transferred onto the outer peripheral surface of the intermediate transfer belt by applying a voltage of a polarity opposite to the charging polarity of the toner to the intermediate transfer belt.

[0378] -Secondary transfer device-

[0379] In the secondary transfer device, the secondary transfer member is arranged on the toner image holding side of the intermediate transfer belt. In addition, the secondary transfer device includes, for example, a back member arranged on the side of the intermediate transfer belt opposite to the toner image holding side together with the secondary transfer member. In the secondary transfer device, a transfer electric field is formed by sandwiching the intermediate transfer belt and the recording medium with the secondary transfer member and the back member, so that the toner image on the intermediate transfer belt is secondarily transferred to the recording medium.

[0380] The secondary transfer member may be a secondary transfer roller or a secondary transfer belt. In addition, the back member may be, for example, a back roller.

[0381] -Other structures of the transfer device-

[0382] This embodiment may be a transfer device that transfers a toner image onto a surface of a recording medium via a plurality of intermediate transfer belts. That is, the transfer device may be, for example, a transfer device that transfers a toner image from an image holder to a first intermediate transfer belt, then transfers the toner image from the first intermediate transfer belt to a second intermediate transfer belt, and then transfers the toner image from the second intermediate transfer belt to a recording medium.

[0383] The transfer device applies the intermediate transfer belt according to the present embodiment described above to at least one of the plurality of intermediate transfer belts.

[0384] (Structure of Image Forming Apparatus)

[0385] The image forming device involved in the present embodiment comprises: an image holder; a charging member for charging the surface of the image holder; an electrostatic latent image forming member for forming an electrostatic latent image on the surface of the charged image holder; a developing member for accommodating an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; an intermediate transfer belt, the outer peripheral surface of which is used to transfer the colorant image; a primary transfer member having a primary transfer member, the primary transfer member primarily transfers the colorant image formed on the surface of the image holder to the outer peripheral surface of the intermediate transfer belt; a secondary transfer member having a secondary transfer member, the secondary transfer member secondarily transfers the colorant image primarily transferred to the outer peripheral surface of the intermediate transfer belt to the surface of a recording medium; and a cleaning device having a cleaning scraper, the cleaning scraper contacts the outer peripheral surface of the intermediate transfer belt and cleans it.

[0386] The image forming apparatus involved in this embodiment is applicable to well-known image forming apparatuses such as an apparatus including a fixing component for fixing the colorant image transferred to the surface of a recording medium; an apparatus including a cleaning device for cleaning the surface of an image holder before charging after transferring the colorant image; an apparatus including an anti-static device for eliminating static electricity by irradiating the surface of the image holder with anti-static light after transferring the colorant image and before charging; and an apparatus including an image holder heating component for increasing the temperature of the image holder to lower the relative temperature.

[0387] The image forming apparatus according to the present embodiment may be any of a dry developing system image forming apparatus and a wet developing system (development system using a liquid developer) image forming apparatus.

[0388] In the image forming apparatus according to the present embodiment, for example, the portion including the image holder may be a cartridge structure (process cartridge) that is detachable from the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.

[0389] (Image Forming Method)

[0390] The image forming method involved in the present embodiment includes: a charging process, which charges the surface of the image retaining body; an electrostatic latent image forming process, which forms an electrostatic latent image on the surface of the charged image retaining body; a developing process, which develops the electrostatic latent image formed on the surface of the image retaining body into a colorant image by using an electrostatic latent image developer containing a colorant having colorant particles; a primary transfer process, which transfers the colorant image formed on the surface of the image retaining body to the outer peripheral surface of the intermediate transfer belt; a secondary transfer process, which transfers the colorant image once transferred to the outer peripheral surface of the intermediate transfer belt to the surface of the recording medium; and a cleaning process, which brings a cleaning scraper into contact with the outer peripheral surface of the intermediate transfer belt and cleans it.

[0391] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.

[0392] The cleaning blade has a double-layer structure consisting of an edge layer and a back layer, wherein the edge layer and the back layer are made of polyurethane resin. Furthermore, the ratio (Hb / Ha) of the hardness Hb (°) of the edge layer to the hardness Ha (°) of the back layer of the cleaning blade is 0.84 or more and 0.93 or less, and the total amount of F and Si present within 200 nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.

[0393] Hereinafter, an example of the image forming apparatus and the image forming method according to the present embodiment will be described with reference to the accompanying drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited thereto. In addition, the main parts shown in the drawings will be described, and the description of other parts will be omitted.

[0394] Figure 1 It is a schematic structural diagram showing the structure of the image forming apparatus according to the present embodiment.

[0395] like Figure 1As shown, the image forming apparatus 100 according to the present embodiment is, for example, an image forming apparatus of an intermediate transfer method generally called a tandem type, and includes: a plurality of image forming units 1Y, 1M, 1C, 1K (an example of a toner image forming apparatus) that form toner images of each color component by an electrophotographic method; a primary transfer unit 10 that sequentially transfers (primary transfers) the toner images of each color component formed by each image forming unit 1Y, 1M, 1C, 1K onto an intermediate transfer belt 15; a secondary transfer unit 20 that transfers (secondary transfers) the superimposed toner images transferred onto the intermediate transfer belt 15 onto a sheet of paper K as a recording medium; and a fixing device 60 that fixes the secondary transferred image onto the sheet of paper K. In addition, the image forming apparatus 100 includes a control unit 40 that controls the operation of each device (unit).

[0396] Each of the image forming units 1Y, 1M, 1C, and 1K of the image forming apparatus 100 includes a photoreceptor 11 (an example of an image holding member) that rotates in the direction of arrow A and holds a toner image formed on the surface.

[0397] Around the photoconductor 11, as an example of a charging component, a charger 12 for charging the photoconductor 11 is provided, and as an example of an electrostatic latent image forming component, a laser exposure device 13 (in the figure, the exposure beam is represented by the symbol Bm) for writing an electrostatic latent image on the photoconductor 11 is provided.

[0398] In addition, around the photosensitive body 11, as an example of a developing member, there is provided a developer 14 that contains colorant of each color component and uses the colorant to visualize the electrostatic latent image on the photosensitive body 11, and there is provided a primary transfer roller 16 that transfers the colorant image of each color component formed on the photosensitive body 11 to the intermediate transfer belt 15 through the primary transfer section 10.

[0399] In addition, a photoreceptor cleaner 17 for removing residual toner on the photoreceptor 11 is provided around the photoreceptor 11, and the electrophotographic devices of the charger 12, the laser exposure device 13, the developer 14, the primary transfer roller 16 and the photoreceptor cleaner 17 are arranged in sequence along the rotation direction of the photoreceptor 11. These image forming units 1Y, 1M, 1C, and 1K are arranged in a substantially straight line from the upstream side of the intermediate transfer belt 15 in the order of yellow (Y), magenta (M), cyan (C), and black (K).

[0400] The intermediate transfer belt 15 passes through various rollers. Figure 1The various rollers include a driving roller 31 that is driven by a motor (not shown) having excellent constant speed to rotate the intermediate transfer belt 15, a supporting roller 32 that supports the intermediate transfer belt 15 that extends substantially linearly along the arrangement direction of the photosensitive bodies 11, a tensioning roller 33 that functions as a correction roller that applies tension to the intermediate transfer belt 15 and prevents the intermediate transfer belt 15 from meandering, a back roller 25 provided on the secondary transfer unit 20, and a cleaning back roller 34 that is provided opposite to an intermediate transfer belt cleaning blade 35 that scrapes off residual toner on the intermediate transfer belt 15.

[0401] The primary transfer unit 10 is composed of a primary transfer roller 16 disposed opposite to the photoreceptor 11 with the intermediate transfer belt 15 interposed therebetween. The primary transfer roller 16 is disposed in pressure contact with the photoreceptor 11 with the intermediate transfer belt 15 interposed therebetween, and a voltage (primary transfer bias) having a polarity opposite to the charged polarity of the toner (negative polarity, the same below) is applied to the primary transfer roller 16. As a result, the toner images on the photoreceptors 11 are electrostatically attracted to the intermediate transfer belt 15 in sequence, and overlapping toner images are formed on the intermediate transfer belt 15.

[0402] The secondary transfer section 20 includes a back roller 25 and a secondary transfer roller 22 disposed on the toner image holding surface side of the intermediate transfer belt 15 .

[0403] The back roller 25 is formed to have a surface resistivity of 1×10 7 Ω / □ or more and 1×10 10 The back roller 25 is arranged on the back side of the intermediate transfer belt 15 and constitutes the counter electrode of the secondary transfer roller 22. The back roller 25 is arranged in contact with a metal power supply roller 26 for stably applying a secondary transfer bias.

[0404] On the other hand, the secondary transfer roller 22 has a volume resistivity of 10 7.5 Ω·cm or more and 10 8.5 The secondary transfer roller 22 is pressed against the back roller 25 with the intermediate transfer belt 15 sandwiched therebetween, and the secondary transfer roller 22 is grounded, and a secondary transfer bias is formed between the secondary transfer roller 22 and the back roller 25, so that the toner image is secondarily transferred onto the paper K conveyed to the secondary transfer unit 20.

[0405] An intermediate transfer belt cleaning blade 35 is provided downstream of the secondary transfer section 20 of the intermediate transfer belt 15 so as to be contactable and releasable to remove residual toner or paper powder on the intermediate transfer belt 15 after the secondary transfer and clean the outer peripheral surface of the intermediate transfer belt 15 .

[0406] In addition, a secondary transfer roller cleaning member 22A is provided on the downstream side of the secondary transfer section 20 of the secondary transfer roller 22 to remove residual toner or paper powder on the secondary transfer roller 22 after the secondary transfer and to clean the outer peripheral surface of the intermediate transfer belt 15. The secondary transfer roller cleaning member 22A may be exemplified by a cleaning blade, but may also be a cleaning roller.

[0407] In addition, the intermediate transfer belt 15 , the primary transfer roller 16 , the secondary transfer roller 22 , and the intermediate transfer belt cleaning blade 35 correspond to an example of a transfer device.

[0408] Here, the image forming apparatus 100 may be configured to include a secondary transfer belt (an example of a secondary transfer member) instead of the secondary transfer roller 22 .

[0409] On the other hand, a reference sensor (home position sensor) 42 is disposed on the upstream side of the yellow image forming unit 1Y, and the reference sensor generates a reference signal that serves as a reference for grasping the timing of image formation in each of the image forming units 1Y, 1M, 1C, and 1K. In addition, an image density sensor 43 for image quality adjustment is disposed on the downstream side of the black image forming unit 1K. The reference sensor 42 recognizes a mark provided on the back side of the intermediate transfer belt 15 and generates a reference signal, and each of the image forming units 1Y, 1M, 1C, and 1K is configured to start image formation in accordance with an instruction from the control unit 40 based on the recognition of the reference signal.

[0410] In addition, in the image forming apparatus involved in the present embodiment, as a conveying component for conveying the paper K, there is provided a paper accommodating portion 50 for accommodating the paper K, a paper supply roller 51 for taking out and conveying the paper K stacked in the paper accommodating portion 50 at a predetermined time, a conveying roller 52 for conveying the paper K delivered by the paper supply roller 51, a conveying guide 53 for conveying the paper K conveyed by the conveying roller 52 into the secondary transfer portion 20, a conveying belt 55 for conveying the paper K conveyed after the secondary transfer by the secondary transfer roller 22 to the fixing device 60, and a fixing entrance guide 56 for guiding the paper K to the fixing device 60.

[0411] Next, a basic image forming process (ie, an image forming method) of the image forming apparatus according to the present embodiment will be described.

[0412] In the image forming apparatus according to this embodiment, image data output from an image reading device (not shown) or a personal computer (PC) (not shown) is processed by an image processing device (not shown) and then image forming operations are performed by image forming units 1Y, 1M, 1C, and 1K.

[0413] In the image processing device, the input image data is subjected to image processing such as shading correction, position shift correction, brightness / color space conversion, gamma correction, frame removal or various image editing such as color editing and motion editing. The image data subjected to image processing is converted into color material grayscale data of four colors, Y, M, C, and K, and output to the laser exposure device 13.

[0414] In the laser exposure device 13, according to the input color material grayscale data, for example, the exposure beam Bm emitted from the semiconductor laser is irradiated onto each photoreceptor 11 of the image forming units 1Y, 1M, 1C, and 1K. In each photoreceptor 11 of the image forming units 1Y, 1M, 1C, and 1K, after the surface is charged by the charger 12, the surface is scanned and exposed by the laser exposure device 13 to form an electrostatic latent image. The formed electrostatic latent image is developed into a toner image of each color of Y, M, C, and K by each image forming unit 1Y, 1M, 1C, and 1K.

[0415] The toner images formed on the photosensitive bodies 11 of the image forming units 1Y, 1M, 1C, and 1K are transferred onto the intermediate transfer belt 15 at the primary transfer section 10 where each photosensitive body 11 contacts the intermediate transfer belt 15. More specifically, at the primary transfer section 10, a voltage (primary transfer bias) having a polarity opposite to the charged polarity (negative polarity) of the toner is applied to the substrate of the intermediate transfer belt 15 by the primary transfer roller 16, and the toner images are sequentially superimposed on the outer peripheral surface of the intermediate transfer belt 15 for primary transfer.

[0416] After the toner images are transferred to the outer peripheral surface of the intermediate transfer belt 15 in sequence, the intermediate transfer belt 15 moves and the toner images are conveyed to the secondary transfer section 20. When the toner images are conveyed to the secondary transfer section 20, the paper supply roller 51 in the conveying member rotates in accordance with the timing when the toner images are conveyed to the secondary transfer section 20, and paper K of a target size is supplied from the paper storage section 50. The paper K supplied by the paper supply roller 51 is conveyed by the conveying roller 52 and reaches the secondary transfer section 20 via the conveying guide 53. Before reaching the secondary transfer section 20, the paper K stops temporarily, and the registration roller (not shown) rotates in accordance with the timing of the movement of the intermediate transfer belt 15 holding the toner images, thereby aligning the position of the paper K with the position of the toner images.

[0417] At the secondary transfer section 20, the secondary transfer roller 22 is pressed against the back roller 25 via the intermediate transfer belt 15. At this time, the paper K conveyed at the timing is sandwiched between the intermediate transfer belt 15 and the secondary transfer roller 22. At this time, if a voltage (secondary transfer bias) having the same polarity as the charged polarity (negative polarity) of the toner is applied from the power supply roller 26, a transfer electric field is formed between the secondary transfer roller 22 and the back roller 25. And, the unfixed toner image held on the intermediate transfer belt 15 is electrostatically transferred onto the paper K at the secondary transfer section 20 pressed by the secondary transfer roller 22 and the back roller 25.

[0418] Then, the paper K to which the toner image is electrostatically transferred is conveyed as it is in a state of being peeled off from the intermediate transfer belt 15 by the secondary transfer roller 22, and is conveyed to the conveying belt 55 provided on the downstream side of the secondary transfer roller 22 in the paper conveying direction. On the conveying belt 55, the paper K is conveyed to the fixing device 60 in accordance with the optimum conveying speed in the fixing device 60. The unfixed toner image on the paper K conveyed to the fixing device 60 is fixed to the paper K by receiving a fixing process with heat and pressure by the fixing device 60. Then, the paper K on which the fixed image is formed is conveyed to a paper discharge accommodating portion (not shown) provided in a discharge portion of the image forming apparatus.

[0419] On the other hand, after the transfer onto the paper K is completed, the residual toner remaining on the intermediate transfer belt 15 is conveyed to the intermediate transfer belt cleaning blade 35 as the intermediate transfer belt 15 rotates, and is removed from the intermediate transfer belt 15 by the intermediate transfer belt cleaning blade 35 .

[0420] As mentioned above, although this embodiment was demonstrated, it is not interpreted as being limited to the said embodiment, Various deformation|transformation, change, and improvement are possible.

[0421] Example

[0422] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0423] [Example 1]

[0424] <Preparation of Electrostatic Latent Image Developer>

[0425] -Preparation of amorphous polyester resin dispersion-

[0426] (Preparation of polyester resin dispersion (APE1))

[0427] Terephthalic acid: 30 mol parts

[0428] Fumaric acid: 70 mol parts

[0429] Bisphenol A ethylene oxide adduct: 5 mol parts

[0430] Bisphenol A propylene oxide adduct: 95 mol parts

[0431] The above materials were placed in a 5-liter flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation column, and the temperature was raised to 210°C over 1 hour. 1 part of tetraethoxytitanium was added to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 230°C over 0.5 hours, and the dehydration condensation reaction was continued at this temperature for 1 hour, and then the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.

[0432] After adding 40 parts of ethyl acetate and 25 parts of 2-butanol to a container equipped with a temperature regulating member and a nitrogen replacement member to prepare a mixed solvent, 100 parts of a polyester resin was gradually added to dissolve it, and a 10% by mass ammonia aqueous solution (equivalent to 3 times the acid value of the resin in terms of molar ratio) was added and stirred for 30 minutes.

[0433] Next, the interior of the container was replaced with dry nitrogen, and the temperature was maintained at 40°C. While stirring the mixed solution, 400 parts of deionized water was added dropwise at a rate of 2 parts / min to emulsify the mixture. After the addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and while stirring, dry nitrogen was bubbled for 48 hours to reduce ethyl acetate and 2-butanol to less than 1,000 ppm, thereby obtaining a resin particle dispersion in which resin particles with a volume average particle size of 200 nm were dispersed. Deionized water was added to the resin particle dispersion to adjust the solid content to 20% by mass, which was used as a polyester resin particle dispersion (APE1).

[0434] -Preparation of Colorant Particle Dispersion-

[0435] (Preparation of Colorant Particle Dispersion Liquid (Black Pigment Dispersion Liquid))

[0436] Carbon black (Rega 1330 manufactured by Cabot Corporation): 250 parts

[0437] Anionic surfactant (NEOGEN SC manufactured by DKS Co. Ltd.): 33 parts (active ingredient: 60%. 8% relative to the colorant)

[0438] Deionized water: 750 parts

[0439] 280 parts of deionized water and 33 parts of anionic surfactants were put into a stainless steel container whose height of the liquid level became about 1 / 3 of the height of the container when all the above components were put into the container. After the surfactant was fully dissolved, all the solid solution pigments were put into the container, and a stirrer was used to stir until there was no pigment that was not wetted, and defoaming was fully carried out. After defoaming, the remaining deionized water was added, and after a homogenizer (IKA company system, ULTRA TURRAX T50) was used to disperse for 10 minutes at 5000 revolutions, a stirrer was used to stir for 1 day and night, and defoaming was carried out. After defoaming, a homogenizer was used again to disperse for 10 minutes at 6000 revolutions, and a stirrer was used to stir for 1 day and night, and defoaming was carried out. Then, a high-pressure impact dispersion machine ULTIMAIZER (SUGINOMACHINE LIMITED system, HJP30006) was used to disperse the dispersion liquid with a pressure of 240MPa. According to the total loading amount and the processing capacity of the device, about 25 dispersions were carried out. The obtained dispersion was left for 72 hours, the precipitate was removed, and deionized water was added to adjust the solid content concentration to 15% to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in the colorant particle dispersion was 135 nm.

[0440] (Preparation of Release Agent Dispersion)

[0441] (Preparation of Release Agent Dispersion (WAX1))

[0442] Paraffin wax (HNP9 manufactured by NIPPON SEIRO CO., LTD., melting temperature 75°C): 270 parts

[0443] Anionic surfactant (NEOGEN RK manufactured by DKS Co. Ltd., active ingredient amount: 60%): 13.5 parts (3.0% based on the release agent in terms of active ingredient)

[0444] Deionized water: 21.6 parts

[0445] The above components were mixed, and the release agent was dissolved in a pressure-dispensing homogenizer (manufactured by Gaulin Co., Ltd., Gaulin Homogenizer) at an internal liquid temperature of 120°C, and then dispersed at a dispersion pressure of 5 MPa for 120 minutes, and then dispersed at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in the release agent dispersion (WAX1) was 225 nm. Then, deionized water was added to adjust the solid content concentration to 20.0%.

[0446] -Preparation of mixed particle dispersion-

[0447] (Preparation of mixed particle dispersion (RW1))

[0448] After mixing 150 parts of a polyester resin particle dispersion (APE1), 20 parts of a release agent particle dispersion (WAX1) and 2.9 parts of an anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company), 1.0% nitric acid was added at 25°C to adjust the pH to 3.0, thereby obtaining a mixed particle dispersion (RW1).

[0449] -Preparation of toner-

[0450] Polyester resin particle dispersion (APE1): 700 parts

[0451] Colorant particle dispersion: 133 parts

[0452] Deionized water: 400 parts

[0453] Anionic surfactant (manufactured by The Dow Chemical Company, Dowfax 2A1): 2.9 parts

[0454] The above components were placed in a 3-liter reaction container equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0. Then, 130 parts of the prepared aluminum sulfate aqueous solution were added while dispersing at 5,000 rpm using a homogenizer (IKA Japan: ULTRA TURRAX T50) and dispersion was carried out for 6 minutes.

[0455] Then, a stirrer and a hood heater were set in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was fully stirred, while the temperature was raised to 40°C at a heating rate of 0.2°C / min, and the temperature was raised at a heating rate of 0.05°C / min from above 40°C. Every 10 minutes, the particle size was measured using Multisizer II (aperture: 50μm, manufactured by Beckman Coulter, Inc.). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added for 5 minutes. After maintaining for 30 minutes, the pH was adjusted to 9.0 using a 1% sodium hydroxide aqueous solution. Then, every 5°C, the pH was adjusted to 9.0 in the same manner, while the temperature was raised to 85°C at a heating rate of 1°C / min, and maintained. The particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM). As a result, aggregation of particles was confirmed at 5.0 hours, so the container was cooled to 30° C. using cooling water over 5 minutes.

[0456] The cooled slurry was passed through a nylon mesh with a pore size of 15 μm to remove coarse powder, and the toner slurry after passing through the mesh was filtered under reduced pressure using an aspirator. The toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C, and stirred and mixed for 30 minutes. Next, the toner was filtered under reduced pressure using an aspirator, and the toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C. After stirring and mixing for 30 minutes, the toner was filtered under reduced pressure again using an aspirator, and the conductivity of the filtrate was measured. This operation was repeated until the conductivity of the filtrate became less than 10 μS / cm, and the toner was washed. After the washed toner was crushed into fine particles using a wet dry granulator (COMIL), it was vacuum dried in an oven at 35°C for 36 hours to obtain toner particles.

[0457] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of the toner particles, and then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. Then, the mixture was sieved using a vibration sieve with an aperture of 45 μm to obtain a toner.

[0458] -Carrier production-

[0459] 500 parts of spherical magnetite particle powder with a volume average particle size of 0.18 μm were added to a Henschel mixer and stirred thoroughly. Then, 5 parts of a titanate coupling agent were added, the temperature was raised to 95° C., and the mixture was stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent.

[0460] Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% ammonia water and 400 parts of water were placed in a 1L four-necked flask and mixed and stirred. Then, while stirring, the temperature was raised to 90°C within 60 minutes, and the reaction was carried out at the same temperature for 180 minutes, then cooled to 30°C, 500 ml of water was added, the supernatant was removed, and the precipitate was washed with water. It was dried at 180°C under reduced pressure, and the coarse powder was removed using a sieve with a mesh of 106 μm to obtain core particles with an average particle size of 38 μm.

[0461] Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio of 10:90, weight average molecular weight of 160,000) were stirred in a stirrer for 90 minutes to obtain a coating resin solution.

[0462] 1000 parts of the core particles and 70 parts of the coating resin solution were placed in a vacuum degassing type kneading coater (the gap between the rotor and the wall surface was 35 mm), maintained at 65°C, stirred at 30 rpm for 30 minutes, and then the temperature was brought to 88°C, the pressure was reduced, toluene was distilled off, degassed and dried. Then, it was passed through a sieve with a mesh size of 75 μm. The shape factor SF2 of the carrier was 104.

[0463] -Production of developer-

[0464] 8 parts of toner and 100 parts of carrier were mixed with a V mixer to prepare a developer.

[0465] -Toner Properties-

[0466] The ratio of the releasing agent present in the region within 800 nm from the surface of the toner particles to the releasing agent in the entire toner particles (surface ratio of the releasing agent) was measured by the above method. The melting temperature of the releasing agent was also measured by the above method.

[0467] <Production of cleaning blade>

[0468] Polycaprolactone polyol (manufactured by Daicel Corporation, PLAXEL205) and polycaprolactone polyol (manufactured by Daicel Corporation, PLAXEL240) were used as hard segment materials of the polyol component. In addition, an acrylic resin containing two or more hydroxyl groups (manufactured by Soken Chemical & Engineering Co., Ltd., ActflowUMB-2005B) was used as a soft segment material, and the hard segment materials and the soft segment materials were mixed at a ratio of 8:2 (mass ratio).

[0469] Next, 4,4'-diphenylmethane diisocyanate (Millionate MT manufactured by Nippon Polyurethane Industry Co., Ltd.) was added as an isocyanate compound to 100 parts of the mixture of the hard segment material and the soft segment material, and the mixture was reacted at 70°C for 3 hours under a nitrogen atmosphere. Next, the above isocyanate compound was further added, and the mixture was reacted at 70°C for 3 hours under a nitrogen atmosphere to obtain a prepolymer.

[0470] Next, the prepolymer was heated to 100°C and defoamed for 1 hour under reduced pressure. Then, a mixture of 1,4-butanediol and trimethylolpropane was added to the prepolymer and mixed for 3 minutes in a manner that prevented bubbles from entering, thereby preparing a back layer forming composition. Next, the back layer forming composition was poured into a centrifugal molding machine and subjected to a curing reaction. Then, it was cut into pieces with a length of 15 mm and a thickness of 1.5 mm to form a back layer.

[0471] Next, an edge layer having a length of 15 mm and a thickness of 0.5 mm was formed in the same manner as the formation of the back surface layer except that the ratio of the hard segment material to the soft segment material was changed to 7:3 (mass ratio).

[0472] In addition, the edge layer and the back layer are integrally formed during centrifugal forming. That is, the molten material of the back layer (the composition for forming the back layer) is injected into a centrifugal forming machine and rotated, and before the composition for forming the back layer is completely solidified (while the material is viscous), the molten material of the edge layer is injected into the centrifugal forming machine, and the centrifugal forming machine is rotated while solidifying the material, and integrally formed to obtain a cleaning blade precursor.

[0473] Modification of contact parts

[0474] The contact portion of the edge layer of the obtained cleaning blade precursor with the intermediate transfer belt was subjected to surface modification treatment using a silicone polymer as follows.

[0475] As the silicone polymer, MODIPER FS770 manufactured by NOF CORPORATION was used. The surface modification treatment was performed as follows: the cleaning blade precursor was immersed in a surface treatment liquid prepared by dispersing and mixing 20 parts of 4,4'-diphenylmethane diisocyanate (4,4-MDI) and 2 parts of silicone polymer with respect to 100 parts of methyl ethyl ketone (MEK) using a ball mill for 3 hours, and then taken out for 120 seconds and dried in an oven at 50°C.

[0476] Through the above operation, a cleaning blade having a double-layer structure of an edge layer and a back layer and having a surface-modified portion in contact with the intermediate transfer belt and having a length of 15 mm and a thickness of 2 mm was obtained.

[0477] -Physical properties of cleaning blade-

[0478] The hardness Ha (°) of the back layer of the cleaning scraper, the hardness Hb (°) of the edge layer, the ratio (Hb / Ha), the ratio of the total amount of F and Si within 200nm from the surface of the edge layer in contact with the intermediate transfer belt to the total amount of F and Si within 5μm from the surface (surface ratio of F, Si), the total amount of F and Si on the surface of the edge layer in contact with the intermediate transfer belt (surface F, Si amount (atm%)), and the total amount of F and Si at a position 50nm from the surface of the edge layer in contact with the intermediate transfer belt (50nm position F, Si amount (atm%)) were measured by the above method.

[0479] <Production of Intermediate Transfer Belt>

[0480] Carbon black particles are dispersed in a polyamic acid solution to prepare a coating liquid 1. The coating liquid is applied to a cylindrical mold to form a coating film, which is then dried. (Substrate 1)

[0481] Then, other carbon black particles are dispersed in the polyamic acid solution to prepare a coating liquid 2, and the coating liquid 2 is applied to the substrate 1 and dried. Then, after a calcination process, cutting is performed.

[0482] Through the above operations, a polyimide intermediate transfer belt was obtained.

[0483] <Image Forming Apparatus>

[0484] The objects obtained above were installed in an image forming apparatus "FUJIFILM Business Innovation Corp. Apeosport-VI C7771" as an electrostatic latent image developer, an intermediate transfer belt, and a cleaning blade for the intermediate transfer belt. In addition, regarding the installation conditions of the cleaning blade for the intermediate transfer belt, the pressing force NF (Normal Force, gf / mm) was set to the conditions described in Table 1, and the angle W / A (Working Angle) was set to 10°.

[0485] [Examples 2 to 9, Comparative Examples 1 to 8]

[0486] <Preparation of Electrostatic Latent Image Developer>

[0487] In Example 1, a release agent is selected for the preparation of a release agent dispersion, and the amount of a mixed particle dispersion (RW1) is adjusted when preparing a colorant, thereby preparing colorant particles that satisfy the "surface ratio of the release agent (%)" and "melting temperature of the release agent (°C)" recorded in Tables 1 and 2 to obtain an electrostatic latent image developer.

[0488] In addition, as the release agent having the melting temperature shown in Table 1 and Table 2, the following compounds were used alone or in combination.

[0489] · Paraffin wax (manufactured by NIPPON SEIRO CO., LTD., melting temperature: 64°C)

[0490] · Paraffin wax (HNP9 manufactured by NIPPON SEIRO CO., LTD., melting temperature 75°C)

[0491] ·Ester wax (manufactured by NOF CORPORATION, melting temperature 82°C)

[0492] Fischer-Tropsch wax (manufactured by NIPPON SEIRO CO., LTD., FNP-0090, melting temperature 90°C)

[0493] <Production of cleaning blade>

[0494] In Example 1, by adjusting the ratio (mass ratio) of the hard segment material to the soft segment material when forming the edge layer and the back layer, selecting the treatment component used for the surface modification treatment of the contact portion of the edge layer of the obtained cleaning blade precursor with the intermediate transfer belt, and adjusting the conditions of the concentration and immersion time of the surface modification treatment, a cleaning blade satisfying the "back layer hardness Ha (°)", "edge layer hardness Hb (°)", "Hb / Ha", "surface ratio of F and Si (%)", "surface F and Si amount (atm%)", and "50nm position F and Si amount (atm%)" described in Tables 1 and 2 was prepared. In addition, the pressing force NF (gf / mm) when the obtained cleaning blade was installed in the image forming apparatus was set to the conditions described in Tables 1 and 2.

[0495] In addition, as blade treatment components shown in Table 1 and Table 2, the following compounds were used.

[0496] Silicone polymer (MODIPER FS770 manufactured by NOF CORPORATION)

[0497] Fluorine compound (MODIPER F206 manufactured by NOF CORPORATION)

[0498] <Evaluation Test>

[0499] Using the image forming apparatus prepared in each of the examples and comparative examples, 10,000 images having an image density of 1% were printed in an environment of a temperature of 28° C. and a humidity of 80% RH.

[0500] · Evaluation of film formation on the intermediate transfer belt

[0501] After the image was printed, the observed image of the intermediate transfer belt surface was binarized in a 100 μm square, and the area ratio occupied by the attached matter was determined and evaluated according to the following criteria.

[0502] G0: No attachment (the attachment ratio is 0%)

[0503] G1: Slight adhesion (the adhesion ratio is less than 1%)

[0504] G2: The percentage of attachment is 1% or more and less than 3%

[0505] G3: The attachment ratio is 3% or more and less than 5%

[0506] G4: The attachment ratio is 5% or more and less than 10%

[0507] G5: The attachment ratio is more than 10%

[0508] Staple Marking

[0509] The presence or absence of staple marks in the printed images was checked and evaluated based on the following criteria.

[0510] A(○): Not generated

[0511] B(×): Produced

[0512] The image forming apparatus was used to print out the toner load adjusted to 0.45 mg / cm 2 As the recording medium, OS coated W paper A4 size (basis weight 127 gsm) manufactured by FUJIFILM Business Innovation Japan Corp. was used. The printed image was set to be an image with a size of 50 mm×50 mm and an image density of 100%.

[0513] As a fixing evaluation device, a device was used in which the fixing unit of ApeosPort-IV C3370 manufactured by FUJIFILM Business Innovation Japan Corp. was removed and modified to allow the nip pressure and fixing temperature to be changed. The processing speed was set to 175 mm / sec, and the obtained fixed image was folded with a weight, and the image quality was evaluated based on the degree of image loss in that portion.

[0514] G1: No image defects are observed

[0515] G2: Image loss is observed but slight

[0516] G3: Slight image loss is observed, but within the allowable range

[0517] G4: Image defects observed

[0518]

[0519]

[0520] As shown in Table 1 and Table 2, it can be seen that the image forming apparatus of this embodiment can suppress toner filming on the surface of the intermediate transfer belt and can suppress the generation of staple marks on the image, compared with the comparative example.

[0521] This embodiment includes the following aspects.

[0522] (((1)))An image forming apparatus comprising:

[0523] Image holding body;

[0524] a charging member for charging the surface of the image holding member;

[0525] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;

[0526] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;

[0527] an intermediate transfer belt, the outer peripheral surface of which is used for transferring the toner image;

[0528] a primary transfer member having a primary transfer part for primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt;

[0529] a secondary transfer member having a secondary transfer component for secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to a surface of a recording medium; and

[0530] A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the intermediate transfer belt, and has a double-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer are composed of a polyurethane resin, the ratio of the hardness Hb of the edge layer to the hardness Ha of the back layer (Hb / Ha) is greater than 0.84 and less than 0.93, and the total amount of F and Si existing within 200nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si existing within 5μm from the surface.

[0531] (((2)))The image forming apparatus according to (((1))), wherein:

[0532] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

[0533] (((3)))The image forming apparatus according to (((1))) or (((2))), wherein:

[0534] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

[0535] (((4)))The image forming apparatus according to any one of (((1))) to (((3))), wherein:

[0536] The cleaning blade has a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer of 0.87 or more and 0.90 or less.

[0537] (((5)))The image forming apparatus according to any one of (((1))) to (((4))), wherein:

[0538] The hardness Hb of the edge layer is greater than or equal to 75° and less than 85°, and the hardness Ha of the back layer is greater than or equal to 85° and less than or equal to 95°.

[0539] (((6)))The image forming device according to (((5))), wherein:

[0540] The hardness Hb of the edge layer is greater than or equal to 77° and less than or equal to 83°, and the hardness Ha of the back surface layer is greater than or equal to 87° and less than or equal to 93°.

[0541] (((7)))The image forming apparatus according to any one of (((1))) to (((6))), wherein:

[0542] In the cleaning blade, a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for 85% or more of a total amount of F and Si present within 5 μm from the surface.

[0543] (((8)))The image forming apparatus according to any one of (((1))) to (((7))), wherein:

[0544] In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 15 atm % or more.

[0545] (((9)))An image forming device according to (((8))), wherein:

[0546] In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 18 atm % or more and 25 atm % or less.

[0547] (((10)))The image forming apparatus according to any one of (((1))) to (((9))), wherein:

[0548] In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more.

[0549] (((11)))The image forming device according to (((10))), wherein:

[0550] In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more and 2.0 atm % or less.

[0551] (((12)))The image forming apparatus according to any one of (((1))) to (((11))), wherein:

[0552] The cleaning blade contains a silicone-based polymer in a surface layer of the edge layer that contacts the intermediate transfer belt.

[0553] (((13)))The image forming apparatus according to any one of (((1))) to (((12))), wherein:

[0554] The cleaning blade contacts the intermediate transfer belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

[0555] (((14)))An image forming method comprising:

[0556] A charging process to charge the surface of the image holding body;

[0557] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;

[0558] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;

[0559] a primary transfer step of primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt;

[0560] a secondary transfer step of secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to the surface of a recording medium; and

[0561] A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the intermediate transfer belt and cleans the same, wherein the cleaning scraper has a double-layer structure consisting of an edge layer and a back layer, wherein the edge layer and the back layer are made of a polyurethane resin, wherein a ratio (Hb / Ha) of a hardness Hb (°) of the edge layer to a hardness Ha (°) of the back layer is greater than or equal to 0.84 and less than or equal to 0.93, and a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of a total amount of F and Si present within 5 μm from the surface.

[0562] According to the invention of (((1))), there is provided an image forming apparatus which suppresses the occurrence of toner filming on the surface of an intermediate transfer belt and suppresses the generation of staple marks on an image, compared to a cleaning scraper having a ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer less than 0.84 or greater than 0.93, or a cleaning scraper having a total amount of F and Si within 200nm from the edge layer on the surface in contact with the intermediate transfer belt less than 75% of the total amount of F and Si within 5μm from the surface.

[0563] According to the invention of (((2))), an image forming apparatus having excellent low-temperature fixing property of an image is provided, compared with an image forming apparatus in which the amount of release agent present in a region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle.

[0564] According to the invention involved in (((3))), an image forming device is provided that has excellent low-temperature fixing property of an image compared to an image forming device in which the melting temperature of a release agent exceeds 75°C, and an image forming device is provided that suppresses colorant filming on the surface of an intermediate transfer belt compared to an image forming device in which the melting temperature of a release agent is lower than 70°C.

[0565] According to the invention involved in (((4))), there is provided an image forming device that suppresses colorant filming on the surface of an intermediate transfer belt compared to an image forming device having a cleaning scraper in which the ratio (Hb / Ha) of the hardness Hb of the edge layer to the hardness Ha of the back layer is less than 0.87 or greater than 0.90.

[0566] According to the invention involved in (((5))) or (((6))), there is provided an image forming device that suppresses the generation of staple marks on an image compared to an image forming device having an edge layer with a hardness of 85° or more or a cleaning scraper having a back layer with a hardness of more than 95°, and an image forming device that achieves excellent cleaning performance and suppresses the wear of the cleaning scraper compared to an image forming device having an edge layer with a hardness of less than 75°, and an image forming device that suppresses the occurrence of lifting on the cleaning scraper compared to an image forming device having a back layer with a hardness of less than 85°.

[0567] According to the invention involved in (((7))), there is provided an image forming device that suppresses colorant filming on the surface of an intermediate transfer belt compared to an image forming device having a cleaning scraper in which the total amount of F and Si present within 200nm from the edge layer of the surface in contact with the intermediate transfer belt is less than 85% of the total amount of F and Si present within 5μm from the surface.

[0568] According to the invention involved in (((8))) or (((9))), there is provided an image forming device that suppresses colorant filming on the surface of an intermediate transfer belt compared to an image forming device having a cleaning scraper in which the total amount of F and Si present on the surface of the edge layer in contact with the intermediate transfer belt is less than 15atm%.

[0569] According to the invention involved in (((10))) or (((11))), there is provided an image forming device which suppresses the occurrence of colorant filming on the surface of the intermediate transfer belt in terms of time, compared to an image forming device having a cleaning scraper in which the total amount of F and Si is less than 0.3atm% at a position 50nm away from the edge layer of the surface in contact with the intermediate transfer belt.

[0570] According to the invention of (((12))), there is provided an image forming apparatus which suppresses the formation of colorant film on the surface of an intermediate transfer belt compared to an image forming apparatus having a cleaning blade with an edge layer whose surface layer in contact with the intermediate transfer belt contains a fluorine-based compound but does not contain a silicone-based polymer.

[0571] According to the invention involved in (((13))), there is provided an image forming device which further suppresses the generation of staple marks on the image compared to an image forming device in which a cleaning scraper contacts the intermediate transfer belt with a pressing force of less than 1.5 gf / mm, and there is provided an image forming device which further suppresses the generation of colorant filming on the surface of the intermediate transfer belt compared to an image forming device in which a cleaning scraper contacts the intermediate transfer belt with a pressing force of more than 3.5 gf / mm.

[0572] According to the invention involved in (((14))), there is provided an image forming method for suppressing colorant filming on the surface of an intermediate transfer belt and suppressing the generation of staple marks on an image, compared to a cleaning process including using a cleaning scraper in which the ratio of the hardness Hb of the edge layer to the hardness Ha of the back layer (Hb / Ha) is less than 0.84 or greater than 0.93, or a cleaning scraper in which the total amount of F and Si present within 200nm from the edge layer on the surface in contact with the intermediate transfer belt is less than 75% of the total amount of F and Si present within 5μm from the surface.

[0573] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

[0574] Explanation of symbols

[0575] 1Y, 1M, 1C, 1K-image forming unit, 10-primary transfer section, 11-photoreceptor, 12-charger, 13-laser exposure device, 14-developer, 15-intermediate transfer belt, 16-primary transfer roller, 17-photoreceptor cleaner, 20-secondary transfer section, 22-secondary transfer roller, 22A-secondary transfer roller cleaning member, 25-back roller, 26-power supply roller, 31-driving roller, 32-support roller, 33-tension imparting roller, 34-cleaning back roller, 35-intermediate transfer belt cleaning blade, 40-control section, 42-reference sensor, 43-image density sensor, 50-paper accommodating section, 51-paper supply roller, 52-transport roller, 53-transport guide, 55-transport belt, 56-fixing inlet guide, 60-fixing device, 100-image forming device.

Claims

1. An image forming device comprising: Image holding body; a charging member for charging the surface of the image holding member; an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member; A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer; an intermediate transfer belt, the outer peripheral surface of which is used for transferring the toner image; a primary transfer member having a primary transfer part for primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt; a secondary transfer member having a secondary transfer component for secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to a surface of a recording medium; and A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the intermediate transfer belt, and has a double-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer are composed of a polyurethane resin, the ratio of the hardness Hb of the edge layer to the hardness Ha of the back layer (Hb / Ha) is greater than 0.84 and less than 0.93, and the total amount of F and Si existing within 200nm from the surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of the total amount of F and Si existing within 5μm from the surface.

2. The image forming apparatus according to claim 1, wherein: The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

3. The image forming apparatus according to claim 1 or 2, wherein: The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

4. The image forming apparatus according to any one of claims 1 to 3, wherein: The cleaning blade has a ratio (Hb / Ha) of a hardness Hb of the edge layer to a hardness Ha of the back layer of 0.87 or more and 0.90 or less.

5. The image forming apparatus according to any one of claims 1 to 4, wherein: The hardness Hb of the edge layer is greater than or equal to 75° and less than 85°, and the hardness Ha of the back layer is greater than or equal to 85° and less than or equal to 95°.

6. The image forming apparatus according to claim 5, wherein: The hardness Hb of the edge layer is greater than or equal to 77° and less than or equal to 83°, and the hardness Ha of the back surface layer is greater than or equal to 87° and less than or equal to 93°.

7. The image forming apparatus according to any one of claims 1 to 6, wherein: In the cleaning blade, a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for 85% or more of a total amount of F and Si present within 5 μm from the surface.

8. The image forming apparatus according to any one of claims 1 to 7, wherein: In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 15 atm % or more.

9. The image forming apparatus according to claim 8, wherein: In the cleaning blade, a total amount of F and Si present on a surface of the edge layer in contact with the intermediate transfer belt is 18 atm % or more and 25 atm % or less.

10. The image forming apparatus according to any one of claims 1 to 9, wherein: In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more.

11. The image forming apparatus according to claim 10, wherein: In the cleaning blade, a total amount of F and Si present at a position 50 nm away from a surface of the edge layer in contact with the intermediate transfer belt is 0.3 atm % or more and 2.0 atm % or less.

12. The image forming apparatus according to any one of claims 1 to 11, wherein: The cleaning blade contains a silicone-based polymer in a surface layer of the edge layer that contacts the intermediate transfer belt.

13. The image forming apparatus according to any one of claims 1 to 12, wherein: The cleaning blade contacts the intermediate transfer belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

14. An image forming method, comprising: A charging process to charge the surface of the image holding body; An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member; A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a primary transfer step of primarily transferring the toner image formed on the surface of the image holding body to the outer peripheral surface of the intermediate transfer belt; A secondary transfer step of secondarily transferring the toner image primarily transferred to the outer peripheral surface of the intermediate transfer belt to the surface of a recording medium; and A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the intermediate transfer belt and cleans the same, wherein the cleaning scraper has a double-layer structure consisting of an edge layer and a back layer, wherein the edge layer and the back layer are made of a polyurethane resin, wherein a ratio (Hb / Ha) of a hardness Hb (°) of the edge layer to a hardness Ha (°) of the back layer is greater than or equal to 0.84 and less than or equal to 0.93, and a total amount of F and Si present within 200 nm from a surface of the edge layer in contact with the intermediate transfer belt accounts for more than 75% of a total amount of F and Si present within 5 μm from the surface.

Citation Information

Patent Citations

  • Cleaning blade

    JP2001051565A

  • Image forming apparatus and process cartridge

    JP2009300751A

  • Process cartridge, image forming apparatus, and image forming method

    JP2021012342A